Cover glass, method for manufacturing cover glass, and display device
The cover glass with an adhesive layer and antireflection layer on a curved surface addresses the challenge of maintaining hardness and adhesion, enhancing visibility in display devices by using an acrylic resin and hollow silica particles.
Patent Information
- Application Number
- JP2023111430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing cover glasses with antireflection layers on curved surfaces face challenges in achieving both excellent surface hardness and adhesion, particularly when using organic films, which are difficult to form and maintain on complex shapes.
A cover glass configuration with a glass substrate having a curved surface area, an adhesive layer containing an acrylic resin and a silane coupling agent, and an antireflection layer made of a resin component, including hollow silica particles, to enhance adhesion and hardness on curved surfaces.
The solution provides a cover glass with excellent surface hardness and adhesion to curved surfaces, ensuring effective antireflection performance and improved visibility in display devices.
Smart Images

Figure 2025008857000003 
Figure 2025008857000004 
Figure 2025008857000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a cover glass, a method for manufacturing the cover glass, and a display device. [Background technology]
[0002] Conventionally, a technique for improving the visibility of a display device by providing an anti-reflection layer on the viewing side surface of a cover glass used for the display of the display device has been known. In recent years, displays such as in-vehicle displays may adopt a curved design for the purpose of improving visibility and design, and thus the demand for a curved cover glass has been increasing.
[0003] Patent Document 1 describes an invention relating to a glass laminate including a glass substrate and a functional layer in which high refractive index layers and low refractive index layers are alternately laminated on at least one main surface of the glass substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-167959 Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors have studied a new cover glass and its manufacturing method that can accommodate more complex shapes of displays, with reference to the technology described in Patent Document 1. In the process, when an anti-reflection layer is provided on a glass substrate having a curved surface, the anti-reflection layer made of a metal oxide film used in conventional in-vehicle display devices can ensure surface hardness, but it may be difficult to form the anti-reflection layer on the curved surface. On the other hand, when an anti-reflection layer made of an organic film that is relatively easy to form on a curved surface is used, it has been found that there is a great deal of room for improvement in the surface hardness and adhesion to the glass substrate of the anti-reflection layer.
[0006] Therefore, an object of the present invention is to provide a cover glass having an antireflection layer that is excellent in surface hardness and adhesion to a curved region present on a main surface of a glass substrate. Another object of the present invention is to provide a method for manufacturing the cover glass, and a display device. [Means for solving the problem]
[0007] As a result of intensive research, the present inventors have found that the above problems can be solved by the following configuration.
[0008] [1] A cover glass for a display device, comprising: a glass substrate having a first main surface and a second main surface, at least a portion of the first main surface being a curved region; an adhesive layer disposed on the first main surface of the glass substrate; and an antireflection layer disposed on the adhesive layer, wherein the antireflection layer contains a resin component, and the adhesive layer contains an acrylic resin as a main component and further contains a silane coupling agent. [2] The cover glass described in [1], wherein the shape of the curved region is a complex curved shape that is curved at any point P included in the curved region in both a first direction that is a tangent direction of the curved region and a second direction that is a tangent direction of the curved region different from the first direction. [3] The cover glass according to [2], wherein the adhesive layer is a resin layer formed using a composition B1 containing an acrylic resin having a reactive group and a silane coupling agent. [4] The cover glass described in [2], wherein the adhesive layer has a resin layer formed using composition B2 containing an acrylic resin having a reactive group, and a primer layer formed using composition B3 containing a silane coupling agent. [5] The cover glass according to [3] or [4], wherein the composition B1 or B2 further contains a polyfunctional urethane (meth)acrylate compound. [6] The cover glass according to any one of [3] to [5], wherein the composition B1 or B2 further contains inorganic oxide particles. [7] The cover glass according to any one of [3] to [6], wherein the silane coupling agent has an ethylenically unsaturated group. [8] The cover glass according to [3], wherein the content of the silane coupling agent is 1 to 15 mass % based on the total solid content of the composition B1. [9] The cover glass according to any one of [3] to [8], wherein the antireflection layer contains an acrylic resin and hollow silica particles.
[10] The cover glass according to any one of [1] to [9], which has a luminous reflectance of 2.0% or less at a wavelength of 360 to 740 nm measured from the antireflection layer side.
[11] The cover glass according to any one of [1] to
[10] , further comprising an antifouling layer on the antireflection layer.
[12] The cover glass according to any one of [1] to
[11] , further comprising an antiglare layer having a concave-convex structure formed on at least a part of a surface of the antireflection layer opposite the adhesive layer, wherein the concave-convex structure has an arithmetic mean height Ra of 10 to 100 nm.
[13] The cover glass according to
[12] , wherein the adhesive layer further contains antiglare particles.
[14] The cover glass according to any one of [1] to
[13] , further comprising a colored layer disposed on the second main surface of the glass substrate, the second main surface having a colored region where the colored layer is laminated and an open region where the colored layer is not laminated.
[15] the first main surface has regions with different radii of curvature; The cover glass according to any one of [1] to
[14] , wherein a region of the first main surface where the antireflection layer is disposed satisfies Requirement 1 described below.
[16] the first main surface has regions with different radii of curvature; The cover glass according to any one of [1] to
[15] , wherein the difference between the total thickness of the adhesive layer and the antireflection layer in the region of the first main surface where the antireflection layer is disposed, that has the smallest radius of curvature, and the total thickness of the adhesive layer and the antireflection layer in the region of the first main surface where the antireflection layer is disposed, is 75 nm or more.
[17] A method for producing a cover glass according to any one of [1] to
[16] , comprising the steps of: preparing a glass substrate having a first main surface and a second main surface, at least a portion of the first main surface being a curved region; preparing a transfer member having a transfer substrate, an anti-reflection layer precursor film, and an adhesive film in this order; a transfer member is laminated onto the glass substrate so that the first main surface of the glass substrate and the adhesive film are in contact with each other, and the adhesive film and the anti-reflection layer precursor film are cured to form an adhesive layer and an anti-reflection layer disposed on the first main surface.
[18] The transfer substrate has a concave-convex structure on a surface in contact with the antireflection layer precursor film, and an antiglare layer having a concave-convex structure on the surface of the antireflection layer precursor film is formed by peeling off the transfer substrate. The manufacturing method according to
[17] .
[19] A display device comprising the cover glass according to any one of [1] to
[16] and a display, wherein the second main surface of the glass base faces the display. Effect of the Invention
[0009] According to the present invention, it is possible to provide a cover glass having an antireflection layer that is excellent in surface hardness and adhesion to a curved region present on a main surface of a glass substrate. Also, according to the present invention, it is possible to provide a method for manufacturing the cover glass and a display device. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the configuration of a cover glass of the present invention. [Diagram 2]FIG. 2 is a cross-sectional view showing an example of the structure of a glass substrate of the cover glass of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described below with reference to the drawings. However, the present invention is not limited to the following embodiments. Various modifications and substitutions can be made to the following embodiments without departing from the scope of the present invention. The dimensions of each component shown in the drawings may be changed for the convenience of explanation and do not necessarily represent the actual dimensions.
[0012] The terms used in this specification have the following meanings: A numerical range expressed using "~" means a range including the numerical values before and after "~" as the upper and lower limits. In the numerical ranges described in stages in this specification, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples. In the present specification, each component may be used alone or in combination of two or more substances corresponding to each component. Here, when two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified. As used herein, a combination of two or more preferred embodiments is a more preferred embodiment.
[0013] The unit is a general term for an atomic group based on one molecule of the above-mentioned monomer formed directly by polymerization of the monomer, and an atomic group obtained by chemically converting a part of the above-mentioned atomic group. The content (mol %) of each unit relative to the total units contained in the polymer can be determined by analyzing the polymer by nuclear magnetic resonance spectroscopy, and can also be determined from the amount of each component used in the production of the polymer. (Meth)acrylate is a general term for acrylate and methacrylate, and (meth)acrylic is a general term for acrylic and methacrylic. The glass transition temperature (Tg) is the midpoint glass transition temperature of a polymer (resin) as measured by differential scanning calorimetry (DSC) method. The number average molecular weight (Mn) and weight average molecular weight (Mw) are values measured by size exclusion chromatography (gel permeation chromatography) using polystyrene as a standard substance. The ratio of Mw to Mn represents the molecular weight distribution, also called Mw / Mn. Transparent means that the average transmittance of visible light (wavelength 400 to 700 nm) is 80% or more.
[0014] [Cover glass] The cover glass of the present invention is a cover glass for a display device, comprising a glass substrate having a first main surface and a second main surface, with at least a portion of the first main surface being a curved region, an adhesive layer disposed on the first main surface of the glass substrate, and an antireflection layer (hereinafter also referred to as "AR layer") disposed on the adhesive layer. The cover glass of the present invention will now be described with reference to the drawings.
[0015] Fig. 1 is a cross-sectional view showing an example of the configuration of the cover glass of the present invention. Fig. 1 shows a cover glass 10 including a glass substrate 1, an adhesive layer 4, and an AR layer (anti-reflection layer) 5 in this order. The glass substrate 1 has a first main surface 11 and a second main surface 12 which is the other main surface opposite to the first main surface 11. A curved region 13 exists in a part of the first main surface 11, and the remainder is a flat region 14. The adhesive layer 4 is disposed on the first main surface 11 of the glass substrate 1, and the AR layer 5 is disposed on the adhesive layer 4. Moreover, in the cover glass 10 shown in FIG. 1, an AFP layer (anti-fouling layer) 6 is further disposed on the AR layer. Further, on the second main surface 12 of the glass substrate 1, there are a colored region 7 where the colored layer 3 is laminated, and an open region 8 where the colored layer 3 is not laminated. When the cover glass 10 is mounted on a display device, the cover glass 10 is positioned, for example, so that the first main surface 11 of the glass base 1 on which the AR layer 5 is arranged faces the viewer, and the second main surface 12 of the glass base 1 on which the colored region 7 is formed faces the display of the display device.
[0016] The cover glass of the present invention is not limited to the embodiment shown in Fig. 1. For example, the cover glass may have a functional layer other than the AR layer and the AFP layer on the second main surface. Such a functional layer may include, for example, an antiglare layer (hereinafter, also referred to as "AG layer"). In addition, the cover glass may not have an AFP layer. Each component of the cover glass will be described in detail below.
[0017] <Glass substrate> The glass substrate is a member having a first main surface and a second main surface, and is, for example, a transparent, plate-like glass member. The glass substrate is made of a general glass. Examples of the glass that forms the glass substrate include non-alkali glass, soda-lime glass, soda-lime silicate glass, aluminosilicate glass, borosilicate glass, lithium aluminosilicate glass, and borosilicate glass. Among them, aluminosilicate glass or lithium aluminosilicate glass is preferable because it is easy to apply a large stress by tempering treatment and can obtain high-strength glass even if it is thin. In particular, when the glass substrate is subjected to a chemical strengthening treatment described below, chemically strengthened glass based on aluminosilicate glass (for example, the "Dragontrail (registered trademark)" series) is preferably used.
[0018] Examples of the shape of the glass substrate include polygonal shapes including rectangular shapes, shapes in which a part of a flat plate is curved or the whole of a curved shape such as circular and elliptical shapes, and three-dimensional shapes. As shown in FIG. 1, a curved region exists on at least a portion of the first main surface of the glass substrate. Here, the "curved region" of the first main surface means a region in which the first radius of curvature R1 described below is 10,000 mm or less, and the "flat region" of the first main surface means a region in which the first radius of curvature R1 described below is more than 10,000 mm.
[0019] When a glass substrate in which at least a portion of its first main surface is a curved region is used as an automotive interior component or a cover glass for a display, etc., the portion placed on these display surfaces is appropriately curved, thereby reducing the viewing angle from the user and improving visibility.
[0020] The curved region of the first main surface may be only a part of the first main surface, or may cover the entire first main surface. The first main surface of the glass substrate may be composed of both a curved region and a flat region. The shapes of the adhesive layer and the AR layer disposed on the curved region follow the shape of the curved region.
[0021] The first radius of curvature R1 of the curved surface is defined as follows. Among the tangent directions at an arbitrary point P on the curved surface, the tangent direction selected so as to satisfy the following condition is defined as the X direction, the tangent direction perpendicular to the X direction is defined as the Y direction, and the normal direction of the principal surface is defined as the Z direction. The X direction is the tangent direction perpendicular to the Z direction in a plane that passes through the above-mentioned point P and includes the Z direction and in which the radius of curvature of the principal surface is the smallest. When there are multiple directions in which the first radius of curvature R1 is the smallest, the first radius of curvature R1 is defined by taking at least one of those directions as the X direction. The first radius of curvature R1 of the curved surface can be appropriately set depending on the application and type of the glass substrate. The first radius of curvature R1 is preferably 1 mm or more, more preferably 50 mm or more, more preferably 100 mm or more, and even more preferably 200 mm or more. The first radius of curvature R1 of the curved surface is 10,000 mm or less, preferably 5,000 mm or less, and more preferably 3,000 mm or less.
[0022] The shape of the curved region constituting at least a part of the first main surface may be curved only in a first direction (X direction) which is a tangent direction of the curved region at any point P included in the curved region, or may be a complex curved shape curved in both the first direction and a second direction (e.g., Y direction) which is a tangent direction of the curved region different from the first direction. When curved in the second direction, the radius of curvature is preferably 1 to 10,000 mm, more preferably 50 to 5,000 mm, further preferably 100 to 3,000 mm, and particularly preferably 200 to 3,000 mm. The radius of curvature of the curved region of the above-mentioned glass substrate may be the same or different in any direction and position of the curved region. The first main surface of the glass substrate may have regions with different radii of curvature. Examples of the first main surface having regions with different radii of curvature include a case where the first main surface is composed of both a curved region and a flat region, and a case where the first main surface has curved regions with different radii of curvature. For the shape of the glass substrate, reference can be made to International Publication No. 2022 / 070611.
[0023] In particular, it is preferable that the curved region of the first main surface on which the colored region is arranged has the above-mentioned complex curved shape, or has a shape that is curved only in the first direction and has a bending angle in the first direction of 45 degrees or more, and it is more preferable that the curved region has the above-mentioned complex curved shape. When the glass substrate has the above-mentioned shape, it is difficult to form an AR layer by the existing method (e.g., sputtering method) for forming an AR layer on a cover panel of a display device. In contrast, according to the cover glass manufacturing method using the transfer decoration method described below, an AR layer with excellent adhesion can be formed even on a glass substrate having the above-mentioned shape, and a high-quality cover panel can be provided.
[0024] The bending angle is defined as follows based on the cross-sectional shape of the glass substrate including a bending direction such as the X direction. Fig. 2 is a cross-sectional view showing an example of the structure of the glass substrate of the cover glass, showing the cross-sectional shape of the glass substrate along the X direction. When there are multiple bending angles in the X direction according to the following definition, it is preferable that at least one bending angle is 45 degrees or more. (i) The cross-sectional shape of the glass base 1A shown in Fig. 2(a) is a shape (V-shape) consisting of a curved region 21 having no inflection point and two flat regions 22 arranged to sandwich the curved region 21. In the case of such a shape, the angle formed between one flat region 22 and the other flat region 22 is defined as the bending angle θ. (ii) The cross-sectional shape of the glass base 1B shown in Fig. 2(b) is a shape that does not have a flat region, is composed of a curved region 31, and has no inflection point (a U-shape). In the case of such a shape, a tangent line T is drawn at a midpoint 32 between an end and a curvature change point closest to the end at each of both ends of the glass base 1B, and the angle formed by the two tangent lines T is defined as the bending angle θ. (iii) When the cross-sectional shape of the glass base is a shape consisting of one flat region and a curved region that is curved along the in-plane direction (X direction) and has no inflection point, the bending angle θ is the angle formed by the flat region and the tangent line T at the midpoint between the end of the curved region and the curvature change point closest to that end. 2(c) is a shape (S-shape) consisting of a curved region 41 with an inflection point Q in the in-plane direction (X direction) without a flat region. In the case of such a shape, at one end of the glass base 1C, a tangent line T1 is drawn at a midpoint 42 between the end and the curvature change point closest to the end, and a tangent line T2 is drawn at the inflection point Q. The angle between the tangent line T1 and the tangent line T2 is defined as the bending angle θ. (v) When the cross-sectional shape of the glass base is a shape consisting of a flat region and a curved region where an inflection point Q is present, the angle between the tangent line T at the inflection point Q and the flat region is defined as the bending angle θ.
[0025] The "flat region" means a portion of the glass base in the above cross-sectional view where the radius of curvature R1 of the intersection line between the paper surface and the main surface of the glass base exceeds 10,000 mm, and the "curved region" means a portion of the glass base in the above cross-sectional view where the radius of curvature R1 of the intersection line is 10,000 mm or less. Moreover, the "point of change of curvature" refers to a point where the change in the radius of curvature R at each position in a section having a length of 50 mm or less exceeds 5%.
[0026] The thickness of the glass substrate is preferably 0.2 to 5.0 mm, more preferably 0.8 to 3.0 mm, and even more preferably 1.0 to 2.5 mm. When the thickness of the glass substrate is within the above range, the glass substrate can be made both lightweight and strong, and the design can be improved when the cover glass is used as a cover panel for an in-vehicle display device.
[0027] The dimensions of the glass substrate can be appropriately selected depending on the application. When the cover glass is used for an in-vehicle display device, the length of the short side of the glass substrate is, for example, 50 to 500 mm, preferably 100 to 300 mm, and the length of the long side of the glass substrate is, for example, 50 to 1500 mm, preferably 100 to 1200 mm.
[0028] The shape, size, etc., of the glass substrate when observed from the normal direction to the main surface (planar view) are appropriately determined depending on the display of the display device in which the cover glass is mounted.
[0029] The glass substrate is preferably strengthened by a chemical strengthening treatment. When the chemical strengthening treatment is performed, a glass for chemical strengthening is used as the glass type. A typical method of chemical strengthening is to immerse a glass substrate formed into a predetermined shape in a molten salt containing an alkali metal such as KNO3, perform ion exchange treatment, and then cool to about room temperature. The treatment conditions such as the temperature of the molten salt and the immersion time may be set so that the surface compressive stress (CS) and the thickness of the compressive stress layer (DOL) are the desired values. The surface compressive stress (CS) of the compressive stress layer is preferably 500 MPa or more, more preferably 600 MPa or more, and even more preferably 700 MPa or more, while CS is preferably 1300 MPa or less. The thickness (DOL) of the compression stress layer is preferably 10 μm or more, more preferably 15 μm or more, further preferably 20 μm or more, particularly preferably 25 μm or more, and is preferably 50 μm or less, more preferably 40 μm or less.
[0030] <Adhesive layer> The cover glass of the present invention is disposed on a first main surface of a glass substrate and includes an adhesive layer containing an acrylic resin and a silane coupling agent.
[0031] In a cover glass having an AR layer on a principal surface of a glass substrate, at least a portion of which is curved, by providing an adhesive layer containing a predetermined component between the principal surface of the glass substrate and the AR layer, it is possible to obtain a cover glass having an AR layer that has excellent adhesion in conformity with the curved shape of the principal surface of the glass substrate and also has excellent surface hardness.
[0032] The adhesive layer contains an acrylic resin as a main component. In this specification, the term "adhesive layer containing acrylic resin" also includes cases where the adhesive layer contains a product (cured product or polycondensation product) obtained by reacting a reactive acrylic resin described below with heat, light, acid, alkali, etc. In addition, "containing acrylic resin as a main component" means that the content of the acrylic resin contained in the adhesive layer is 50% by mass or more based on the total amount of the adhesive layer. The adhesive layer contains a silane coupling agent in addition to the acrylic resin. In this specification, the term "adhesive layer containing a silane coupling agent" also includes cases where the adhesive layer contains at least one of a hydrolysate of a silane coupling agent and a hydrolysis condensate of a silane coupling agent.
[0033] (Acrylic resin) The acrylic resin is a polymer having units derived from a (meth)acrylate compound. The (meth)acrylate compound means an ester compound of (meth)acrylic acid and alcohol.The (meth)acrylate compound may be, for example, (meth)acrylate monomer, (meth)acrylate oligomer, (meth)acrylate polymer, or other (meth)acrylate compound; urethane (meth)acrylate monomer, urethane (meth)acrylate oligomer, urethane (meth)acrylate polymer, or other (meth)acrylate compound; and silicon (meth)acrylate monomer, silicon (meth)acrylate oligomer, silicon (meth)acrylate polymer, or other (meth)acrylate compound. These may be used alone or in combination of two or more.
[0034] The acrylic resin contained in the adhesive layer may be a product (cured product or polycondensation product) obtained by reaction of an acrylic resin having a reactive group (hereinafter also referred to as a "reactive acrylic resin"), or may be an acrylic resin not having a reactive group (hereinafter also referred to as a "non-reactive acrylic resin"). Examples of the reactive group contained in the reactive acrylic resin include an ethylenically unsaturated group, a carboxy group, a hydroxyl group, a sulfo group, and an epoxy group. The reactive acrylic resin is preferably an ethylenically unsaturated group-containing acrylic resin.
[0035] The adhesive layer preferably contains a reactive acrylic resin, because the inclusion of the reactive acrylic resin increases the crosslink density of the adhesive layer, and the AR layer disposed on the adhesive layer has superior surface hardness.
[0036] In this specification, the weight average molecular weight (Mw) of the compounds referred to as "resin" and "polymer" is preferably 2,000 or more, and more preferably 3,000 or more.
[0037] The weight average molecular weight (Mw) of the acrylic resin is preferably from 5,000 to 100,000, more preferably from 6,000 to 95,000, and even more preferably from 9,000 to 90,000. The glass transition temperature (Tg) of the acrylic resin is, for example, preferably from 40 to 120°C, and more preferably from 40 to 110°C.
[0038] The content of the acrylic resin in the adhesive layer is preferably 50 to 90 mass %, more preferably 50 to 85 mass %, and even more preferably 55 to 80 mass %, based on the total amount of the adhesive layer.
[0039] (Silane coupling agent) Silane coupling agent is a silicon-containing compound having a reactive group and a hydrolyzable group in the molecule that reacts with organic material.As mentioned above, the silane coupling agent contained in the adhesive layer may be either the hydrolyzate of silane coupling agent or the hydrolysis condensate of silane coupling agent.
[0040] The silane coupling agent contained in the adhesive layer is appropriately selected depending on the type of acrylic resin contained in the adhesive layer and the components contained in the AR layer. An example of the silane coupling agent is a compound represented by the chemical formula X-Si(R)3. In the above chemical formula, X is a reactive group that reacts with an organic material, and examples thereof include groups containing ethylenically unsaturated groups such as vinyl groups, allyl groups, (meth)acryloyl groups, and styryl groups, as well as epoxy groups, amino groups, mercapto groups, and sulfide groups. Among these, the silane coupling agent preferably contains an ethylenically unsaturated group, and more preferably contains a (meth)acryloyl group. R is a hydrolyzable group, for example, an alkoxy group, a halogen atom, an acyloxy group, an alkenyloxy group, and an isocyanate group. Among them, an alkoxy group is preferable, and a methoxy group or an ethoxy group is more preferable.
[0041] Examples of silane coupling agents include vinyltrimethoxysilane, vinyltriethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and bis(triethoxysilylpropyl)tetrasulfide. Among these, silane coupling agents containing an ethylenically unsaturated group-containing group (vinyltrimethoxysilane, vinyltriethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, etc.) are preferred, and silane coupling agents containing a (meth)acryloyl group (3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, etc.) are more preferred.
[0042] The content of the silane coupling agent in the adhesive layer is preferably 1.5 to 10 mass %, more preferably 2.5 to 7.5 mass %, based on the total amount of the adhesive layer.
[0043] The adhesive layer may contain a resin other than the acrylic resin (hereinafter also referred to as a "non-acrylic resin"). Non-acrylic resins include polyester resins, epoxy resins, urethane resins, polyamide resins, phenolic resins, and urea resins. The non-acrylic resin may be a product (cured product or polycondensation product) obtained by reacting the non-acrylic resin with heat, light, acid, alkali, or the like. The non-acrylic resin may be a non-reactive resin that does not react or shows almost no reactivity when irradiated with active energy rays (typically, ultraviolet rays).
[0044] The polyester resin is a polymer in which a unit derived from a polyvalent carboxylic acid and a unit derived from a polyhydric alcohol are linked by an ester bond. The polyester resin may have a unit other than the above two types of units (for example, a unit derived from a hydroxycarboxylic acid compound). Examples of polycarboxylic acids include aromatic polycarboxylic acids and aliphatic polycarboxylic acids. Among them, it is preferable to use aromatic polycarboxylic acids, and it is more preferable to use both aromatic polycarboxylic acids and aliphatic polycarboxylic acids. The number of carboxy groups in the polycarboxylic acid is preferably 2 to 4. The polyhydric alcohol is preferably a polyhydric alcohol having 2 to 10 carbon atoms. The number of hydroxyl groups in the polyhydric alcohol is preferably 2 to 4.
[0045] An epoxy resin is a compound having two or more epoxy groups in a molecule. As the epoxy resin, an aromatic compound having a glycidyloxy group such as bisphenol A-diglycidyl ether and an oligomer thereof are preferable.
[0046] The weight average molecular weight (Mw) of the non-acrylic resin is preferably from 5,000 to 100,000, and more preferably from 6,000 to 95,000.
[0047] The adhesive layer may include hardness imparting particles. In this specification, the hardness-imparting particles refer to particles having a primary particle diameter of 10 to 100 nm. Examples of hardness-imparting particles include inorganic oxide particles such as silica (SiO2) particles, alumina particles, titania particles, tin oxide particles, antimony-doped tin oxide (ATO) particles, zinc oxide particles, and zirconia oxide particles. The surface of the hardness imparting particles may be modified with an ethylenically unsaturated group-containing group, preferably a (meth)acryloyl group. Among these, silica particles or alumina particles are preferred, and silica particles the surface of which has been modified with an ethylenically unsaturated group-containing group, or alumina particles the surface of which has been modified with an ethylenically unsaturated group-containing group are more preferred. By including such inorganic oxide particles, the hardness of the AR layer can be improved.
[0048] The adhesive layer may further contain antiglare property imparting particles. The antiglare property imparting particles in the present invention refer to particles having a primary particle diameter of 100 to 500 nm, and are therefore distinguished from the above-mentioned hardness imparting particles. Examples of the anti-glare property-imparting particles include inorganic fine particles such as silica, clay, talc, calcium carbonate, calcium sulfate, barium sulfate, aluminum silicate, titanium oxide, synthetic zeolite, alumina, and smectite, as well as organic fine particles such as styrene resin, urethane resin, benzoguanamine resin, silicone resin, and acrylic resin. By including such antiglare particles, the adhesive layer functions as an AG layer.
[0049] The total content of the inorganic oxide particles and the antiglare property-imparting particles is preferably from 1 to 55% by mass, more preferably from 10 to 50% by mass, and even more preferably from 12 to 40% by mass, based on the total amount of the adhesive layer.
[0050] The average primary particle diameter of the hardness-imparting particles and the anti-glare property-imparting particles is a value obtained by randomly selecting 100 particles from an image of the cross section of the adhesive layer obtained by an electron microscope and arithmetically averaging the primary particle diameters of each particle measured using image processing software.
[0051] (Composition for forming adhesive layer) The adhesive layer may be a layer formed using a composition for forming an adhesive layer (hereinafter also referred to as "composition B") that contains components that constitute the adhesive layer. Examples of composition B include composition B1, which contains an acrylic resin and a silane coupling agent, and optionally contains at least one component selected from the group consisting of a non-acrylic resin, an inorganic oxide particle, a (meth)acrylate compound, a polymerization initiator, and a solvent; composition B2, which contains at least an acrylic resin, and optionally contains at least one component selected from the group consisting of a silane coupling agent, a non-acrylic resin, an inorganic oxide particle, a (meth)acrylate compound, a polymerization initiator, and a solvent; and composition B3, which contains at least a silane coupling agent, and optionally contains at least one component selected from the group consisting of an acrylic resin, a non-acrylic resin, an inorganic oxide particle, a (meth)acrylate compound, a polymerization initiator, and a solvent. The adhesive layer may be a resin layer formed using composition B1, or may include two layers: a resin layer formed using composition B2 and a primer layer formed using composition B3.
[0052] Each component contained in composition B (any of compositions B1, B2, and B3) will be described. The method for forming an adhesive layer using composition B will be described in detail later.
[0053] The acrylic resin, the silane coupling agent, the non-acrylic resin, and the inorganic oxide particles contained in the composition B, including preferred embodiments thereof, are as already explained. The acrylic resin contained in composition B is preferably an acrylic resin having a reactive group. In addition, the content of the acrylic resin, silane coupling agent, non-acrylic resin, and inorganic oxide particles relative to the total solid content of composition B may be the same as the content of each component relative to the total amount of the adhesive layer, including more preferred ranges.
[0054] Composition B may contain a (meth)acrylate compound selected from the group consisting of (meth)acrylate monomers and (meth)acrylate oligomers. The (meth)acrylate monomer is a compound having at least one (meth)acryloyl group. The molecular weight of the (meth)acrylate monomer is preferably less than 1,000, and more preferably 800 or less. The (meth)acrylate oligomer is an oligomer compound having a plurality of units derived from a (meth)acrylate monomer. The molecular weight of the (meth)acrylate oligomer (when the molecular weight has a distribution, the weight average molecular weight (Mw)) is preferably 1,000 or more and less than 3,000, more preferably 1,000 or more and less than 2,000.
[0055] Examples of the (meth)acrylate compound include urethane (meth)acrylate compounds, silicon (meth)acrylate compounds, and (meth)acrylate compounds other than urethane (meth)acrylate compounds and silicon (meth)acrylate compounds.
[0056] Examples of the urethane (meth)acrylate compound include a urethane (meth)acrylate monomer having at least one (meth)acryloyl group and at least one urethane bond in the molecule, and a urethane (meth)acrylate oligomer having a plurality of units derived from the urethane (meth)acrylate monomer. The urethane (meth)acrylate compound can be prepared, for example, by reacting a polycarbonate diol, a (meth)acrylate compound containing a hydroxyl group and an unsaturated double bond group in the molecule, and a polyisocyanate.
[0057] Examples of the silicon (meth)acrylate compound include a silicon (meth)acrylate monomer having at least one (meth)acryloyl group and at least one siloxane bond in the molecule, and a silicon (meth)acrylate oligomer having a plurality of units derived from the silicon (meth)acrylate monomer. In the silicon (meth)acrylate compound, a functional group containing a fluorine atom may be bonded to a silicon atom constituting a siloxane bond.
[0058] Examples of (meth)acrylate compounds other than urethane (meth)acrylate compounds and silicon (meth)acrylate compounds include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, acrylic acid, methacrylic acid, isostearyl (meth)acrylate, ethoxylated o-phenylphenol acrylate, methoxypolyethylene glycol acrylate, methoxypolyethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 2-ethylhexyl (meth)acrylate, acrylic acid, methacrylic acid, isostearyl (meth)acrylate, ethoxylated o-phenylphenol ... Examples of the (meth)acrylate monomer include those selected from the group consisting of acryloyloxyethyl succinate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, 2-hydroxy-3-methoxypropyl (meth)acrylate, N-methylol (meth)acrylamide, and N-hydroxy(meth)acrylamide, as well as (meth)acrylate oligomers having a plurality of units derived from these (meth)acrylate monomers.
[0059] From the viewpoints of adhesion to the AR layer, surface hardness of the AR layer, and formability to the curved shape of the glass substrate, composition B preferably contains a polyfunctional (meth)acrylate compound, and more preferably contains at least one selected from the group consisting of a polyfunctional urethane (meth)acrylate compound and a polyfunctional silicon (meth)acrylate compound. With respect to the (meth)acrylate compound, the term "polyfunctional" means that the compound has a plurality of (meth)acryloyl groups in the molecule. The acrylate equivalent of the polyfunctional (meth)acrylate compound may be 100 to 200 g / eq., preferably 110 to 180 g / eq., and more preferably 115 to 160 g / eq.
[0060] From the viewpoints of the surface hardness of the AR layer and the formability to the curved surface shape of the glass substrate, it is preferable that composition B further contains a polyfunctional urethane (meth)acrylate compound. Among these, from the viewpoint of further improving the low tackiness of the coating film formed using composition B, it is more preferable that composition B contains an acrylic resin having a weight average molecular weight (Mw) of 5,000 to 100,000 and a polyfunctional urethane (meth)acrylate compound having an acrylate equivalent of 100 to 200 g / eq.
[0061] When composition B contains a polyfunctional urethane (meth)acrylate compound, the content of the polyfunctional urethane (meth)acrylate compound is preferably 5 to 70 mass%, more preferably 10 to 70 mass%, and even more preferably 13 to 68 mass%, based on the total solid content of composition B.
[0062] Composition B preferably contains an acrylic resin and a polyfunctional silicon (meth)acrylate compound or inorganic oxide particles. The polyfunctional silicon (meth)acrylate compound or inorganic oxide particles tend to increase the rigidity of the adhesive layer, suppress changes in appearance and curling of the adhesive layer, reduce tackiness, and tend to increase abrasion resistance.
[0063] When composition B contains a polyfunctional silicone (meth)acrylate compound, the content of the polyfunctional silicone (meth)acrylate compound is preferably 0.1 to 50 mass%, more preferably 1 to 45 mass%, and even more preferably 1.5 to 40 mass%, based on the total solid content of composition B.
[0064] Among them, it is particularly preferable that composition B contains an acrylic resin, a polyfunctional urethane (meth)acrylate compound, and inorganic oxide particles.
[0065] Composition B may contain a polymerization initiator, and when composition B contains a reactive acrylic resin, it preferably contains a polymerization initiator. Examples of the polymerization initiator include a thermal polymerization initiator and a photopolymerization initiator. An appropriate type can be selected depending on the type of reactive group possessed by the resin contained in composition B. Composition B may contain either a thermal polymerization initiator or a photopolymerization initiator, or may contain both.
[0066] Composition B preferably contains a photopolymerization initiator. Examples of the photopolymerization initiator include an alkylphenone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a titanocene-based photopolymerization initiator, and an oxime ester-based polymerization initiator. The content of the polymerization initiator is preferably from 0.01 to 10 mass %, more preferably from 1 to 10 mass %, based on the total solid content of composition B.
[0067] Composition B may contain a solvent. The solvent is appropriately selected taking into consideration the components contained in composition B, the type of substrate, the method for forming the adhesive layer, and the like. Examples of the solvent include water; aromatic solvents such as toluene and xylene; ketone-based solvents such as methyl ethyl ketone, acetone, methyl isobutyl ketone and cyclohexanone; ether-based solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether (PGM), anisole and phenetole; ester-based solvents such as ethyl acetate, butyl acetate, isopropyl acetate and ethylene glycol diacetate; amide-based solvents such as dimethylformamide, diethylformamide and N-methylpyrrolidone; cellosolve-based solvents such as methyl cellosolve, ethyl cellosolve and butyl cellosolve; alcohol-based solvents such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol and diacetone alcohol (DAA); and halogen-based solvents such as dichloromethane and chloroform.
[0068] Composition B may contain various additives as necessary, such as a tackifier, an antifoaming agent, an antistatic agent, a plasticizer, a surfactant, an antioxidant, an ultraviolet absorber, a surface conditioner, a leveling agent, and a light stabilizer (e.g., a hindered amine light stabilizer (HALS)).
[0069] Composition B preferably has a property of being cured by active energy rays. The active energy rays are ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. Composition B is preferably an ultraviolet-curable composition containing a photopolymerization initiator.
[0070] The adhesive layer may have a single-layer structure consisting of only one layer, or may have a multi-layer structure consisting of multiple layers. An example of an adhesive layer having a single-layer structure is an adhesive layer having only a resin layer containing at least an acrylic resin and a silane coupling agent, which is formed using the composition B1. An example of an adhesive layer having a multilayer structure is an adhesive layer having a resin layer containing at least an acrylic resin formed using the above composition B2, and a primer layer containing at least a silane coupling agent formed using the above composition B3. In either case, it is preferable that no other layer exists between the adhesive layer and the first main surface of the glass substrate, and that the adhesive layer and the first main surface of the glass substrate are in direct contact with each other.
[0071] When the adhesive layer has a resin layer containing at least an acrylic resin and a primer layer containing at least a silane coupling agent, it is preferable for the adhesive layer to have one resin layer and one or two primer layers arranged adjacent to the resin layer, and it is more preferable for the adhesive layer to have one resin layer and one primer layer arranged adjacent to the resin layer. When the adhesive layer has a multi-layer structure and has only one primer layer, the primer layer is preferably disposed on the surface of the adhesive layer facing the glass substrate.
[0072] The compositions B1 and B2 which become the resin layers preferably further contain a polyfunctional silicon (meth)acrylate compound and inorganic oxide particles. In this case, the preferred ranges of the content of the polyfunctional silicon (meth)acrylate compound and the content of the inorganic oxide particles in the compositions B1 and B2 are as described above. It is also preferred that the compositions B1 and B2 further contain a polyfunctional urethane (meth)acrylate compound. In this case, the preferred range of the content of the polyfunctional urethane (meth)acrylate compound in the composition B1 or B2 is as described above. When compositions B1 and B2 contain a solvent, the solvent is preferably an ester-based solvent, an ether-based solvent, an alcohol-based solvent or a ketone-based solvent.
[0073] The content of the silane coupling agent in the composition B1 is preferably from 0.5 to 20 mass %, more preferably from 1 to 15 mass %, based on the total solid content of each composition. Composition B2 may or may not contain a silane coupling agent.
[0074] Composition B3 which becomes the primer layer preferably further contains a solvent in addition to the silane coupling agent, and more preferably contains at least one solvent selected from the group consisting of water and alcohol-based solvents. Examples of alcohol-based solvents include monoalcohol compounds having one hydroxyl group per molecule (e.g., methanol, ethanol, isopropanol, etc.), glycol compounds having two hydroxyl groups per molecule (e.g., ethylene glycol, propylene glycol, diethylene glycol, etc.), and polyalcohols having three or more hydroxyl groups per molecule.
[0075] The content of the silane coupling agent in the composition B3 is preferably 80 to 100 mass %, and more preferably 90 to 100 mass %, based on the total solid content of the composition B3. The content of the silane coupling agent in composition B3 is preferably 0.1 to 2 mass %, and more preferably 0.2 to 1.5 mass %, based on the total amount of composition B3.
[0076] The thickness of the adhesive layer is preferably from 2 to 20 μm, and more preferably from 3 to 15 μm, in terms of better adhesion and strength. When the adhesive layer has a multi-layer structure including a resin layer containing at least an acrylic resin and a primer layer containing at least a silane coupling agent, the thickness of the resin layer is preferably 2 to 20 μm, more preferably 3 to 10 μm, in terms of better adhesion and strength. Also, the thickness of the primer layer is preferably 1 to 80 nm, more preferably 3 to 50 nm, in terms of excellent balance between adhesion and permeability.
[0077] The thickness of the layers constituting the cover glass such as the adhesive layer and the AR layer can be measured using a non-contact measuring device by a stage scanning type laser probe method (for example, "NH-3MAs" manufactured by Mitaka Kohki Co., Ltd.). Also, the thickness of the layers constituting the cover glass can be measured by observing the cross-section in the thickness direction of each layer using a scanning electron microscope (SEM: Scanning Electron Microscope).
[0078] <AR layer> The cover glass of the present invention includes an AR (Anti-Reflection) layer disposed on the adhesive layer. The AR layer is a layer containing a resin component, which provides the cover glass with the effect of reducing reflectance, reduces glare due to reflected light, and has the function of improving the visibility of the display image when the cover glass is used in a display device.
[0079] Examples of the AR layer include an AR layer containing a refractive index lowering component and a resin component, and an AR layer containing a refractive index lowering component and an acrylic resin is preferred. In this specification, the "AR layer containing a resin component" or the "AR layer containing an acrylic resin" also includes the case where the AR layer contains a product (cured product or polycondensate) obtained by reacting a reactive resin or a reactive acrylic resin described later with heat, light, acid, alkali, etc.
[0080] (Refractive index lowering component) The refractive index lowering component contained in the AR layer is a component that has a function of lowering the refractive index of the AR layer. The refractive index lowering component is, for example, in the form of particles (hereinafter, also referred to as "refractive index lowering particles").
[0081] The refractive index reducing particle can be, for example, hollow silica particle. Hollow silica particle has a hollow structure, which is at least one of a structure filled with gas inside and a porous structure containing gas. Since the refractive index decreases in inverse proportion to the occupancy rate of gas, the refractive index of hollow silica particle is lower than that of silica particle that does not have the hollow structure. As a result, hollow silica particle can reduce the refractive index of AR layer while maintaining the strength of AR layer. An example of a commercially available hollow silica particle is Sururia 4320 (manufactured by JGC Catalysts and Chemicals, Ltd.).
[0082] The refractive index-reducing particles may be silica particles having a nanoporous structure formed in at least a portion of the interior and surface thereof. The nanoporous structure is formed depending on the morphology, structure, and aggregation state of the silica particles, and the dispersion state inside the coating film.
[0083] The average primary particle diameter of the refractive index-reducing particles is preferably 60 to 200 nm. The average primary particle diameter of the refractive index-reducing particles is a value obtained by arbitrarily selecting 100 refractive index-reducing particles from an image of the cross section of the AR layer obtained by an electron microscope, and arithmetically averaging the primary particle diameters of each particle measured using image processing software.
[0084] The content of the refractive index lowering component is preferably 35 to 70 mass %, and more preferably 37.5 to 60 mass %, based on the total amount of the AR layer, in terms of excellent antireflection properties.
[0085] (Resin component) Examples of the resin component contained in the AR layer include acrylic resin, polyester resin, epoxy resin, urethane resin, polyamide resin, phenol resin, urea resin, and fluororesin. In particular, the AR layer preferably contains an acrylic resin.
[0086] The acrylic resin, polyester resin, epoxy resin, urethane resin, polyamide resin, phenol resin, and urea resin contained in the AR layer, including preferred embodiments, are as already described as the acrylic resin or non-acrylic resin contained in the adhesive layer.
[0087] The fluororesin is a resin that does not contain a siloxane bond and has at least a portion of the hydrogen atoms in the alkyl chain of the resin substituted with fluorine atoms. Examples of the fluororesin include perfluorooctyl acrylate and acrylic modified perfluoropolyether. The fluororesin may have a (meth)acryloyl group partially substituted with fluorine atoms. The content of the fluororesin is preferably from 0.1 to 10 mass %, more preferably from 1 to 8 mass %, and further preferably from 1.5 to 7 mass %, based on the total amount of the AR layer.
[0088] When the AR layer contains an acrylic resin, the acrylic resin contained in the AR layer may be the same as or different from the acrylic resin contained in the adhesive layer. The acrylic resin contained in the AR layer and the acrylic resin contained in the adhesive layer are preferably the same. Here, the acrylic resin being the same means that the units constituting the acrylic resin are units derived from the same (meth)acrylate monomer. This is because the adhesion between the adhesive layer and the AR layer is improved, and peeling between the layers is less likely to occur.
[0089] The content of the resin component in the AR layer is preferably from 5 to 40% by mass, more preferably from 10 to 30% by mass, and further preferably from 15 to 25% by mass, based on the total amount of the AR layer.
[0090] The AR layer may contain inorganic oxide particles (excluding refractive index reducing particles). The inorganic oxide particles contained in the AR layer, including preferred embodiments thereof, are as already described for the inorganic oxide particles contained in the adhesive layer.
[0091] (AR layer forming composition) The AR layer may be a layer formed using a composition for forming an AR layer (hereinafter also referred to as "composition R") containing components that constitute the AR layer. Examples of composition R include compositions that contain a refractive index reducing component and a resin component, and optionally contain at least one component selected from the group consisting of inorganic oxide particles, a (meth)acrylate compound, a polymerization initiator, and a solvent.
[0092] Each component contained in composition R will be described. The method for forming the AR layer using the composition R will be described later in detail.
[0093] The refractive index lowering component, the resin component, and the inorganic oxide particles contained in the composition R are as already explained. Furthermore, the content of the refractive index lowering component and the resin component relative to the total solid content of the composition R may be the same as the content of each component relative to the total amount of the AR layer, including more preferred ranges.
[0094] Composition R may contain a (meth)acrylate compound selected from the group consisting of (meth)acrylate monomers and (meth)acrylate oligomers. Examples of the (meth)acrylate compound contained in composition R include urethane (meth)acrylate compounds, silicon (meth)acrylate compounds, and (meth)acrylate compounds other than urethane (meth)acrylate compounds and silicon (meth)acrylate compounds. From the viewpoints of adhesion to the adhesive layer, the surface hardness of the AR layer, and the transparency of the AR layer, composition R preferably contains a polyfunctional (meth)acrylate compound, and more preferably contains at least one selected from the group consisting of a polyfunctional urethane (meth)acrylate compound and a polyfunctional silicon (meth)acrylate compound. The definitions and preferred embodiments of the (meth)acrylate compound, urethane (meth)acrylate compound, silicon (meth)acrylate compound, and polyfunctional (meth)acrylate compound contained in composition R may be the same as those of each (meth)acrylate compound contained in composition B.
[0095] Composition R preferably contains a refractive index reducing component, an acrylic resin, and a polyfunctional urethane (meth)acrylate compound, in order to improve the low tack and antifouling properties of the AR layer and to improve the adhesion between the adhesive layer and the AR layer. When composition R contains a polyfunctional urethane (meth)acrylate compound, the content of the polyfunctional urethane (meth)acrylate compound is preferably 5 to 70 mass %, more preferably 10 to 70 mass %, and even more preferably 13 to 68 mass %, based on the total solid content of composition R.
[0096] Moreover, composition R preferably contains a refractive index lowering component, an acrylic resin, and a polyfunctional silicon (meth)acrylate compound. When composition R contains a polyfunctional silicone (meth)acrylate compound, the content of the polyfunctional silicone (meth)acrylate compound is preferably 5 to 50 mass %, more preferably 10 to 48 mass %, and even more preferably 13 to 48 mass %, based on the total solid content of composition R.
[0097] Among them, it is particularly preferable that composition R contains a refractive index lowering component, an acrylic resin, a polyfunctional urethane (meth)acrylate compound, and a polyfunctional silicon (meth)acrylate compound containing a fluorine atom.
[0098] Composition R may contain a polymerization initiator, and when composition R contains a reactive acrylic resin, it preferably contains a polymerization initiator. Examples of the polymerization initiator include a thermal polymerization initiator and a photopolymerization initiator, and an appropriate type can be selected depending on the type of reactive group possessed by the resin component contained in the composition R. The composition R may contain either a thermal polymerization initiator or a photopolymerization initiator, or may contain both.
[0099] Composition R preferably contains a photopolymerization initiator. Examples of the photopolymerization initiator include an alkylphenone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a titanocene-based photopolymerization initiator, and an oxime ester-based polymerization initiator. Among them, at least one selected from the group consisting of 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2,2-dimethoxy-1,2-diphenylethan-1-one is preferred. The content of the polymerization initiator is preferably from 0.01 to 10 mass %, more preferably from 1 to 10 mass %, based on the total solid content of the composition R.
[0100] The composition R may contain a solvent. The solvent is appropriately selected in consideration of the components contained in the composition R, the type of the substrate, the method for forming the AR layer, and the like. The solvent can be selected from those exemplified as the solvent contained in the composition B. Among them, ester-based solvents, ether-based solvents, alcohol-based solvents, and ketone-based solvents are preferable.
[0101] Composition R preferably has a property of being cured by active energy rays. The active energy rays are ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays. Composition R is preferably an ultraviolet-curable composition containing a photopolymerization initiator.
[0102] The thickness of the AR layer may be, for example, 10 to 300 nm. The thickness of the AR layer is preferably 15 nm or more, more preferably 40 nm or more, and even more preferably 60 nm or more. The thickness of the AR layer is preferably 200 nm or less, more preferably 180 nm or less, and even more preferably 150 nm or less.
[0103] <Other layers> The cover glass may further comprise other layers besides the glass substrate, adhesive layer and AR layer. Examples of other layers that the cover glass may further include an antiglare layer (hereinafter also referred to as an "AG layer"), an AFP layer, and a colored layer.
[0104] (AG layer) The AG (Anti-Glare) layer is a layer that imparts anti-glare properties to the cover glass. The AG layer is usually a layer disposed on the first main surface side of a glass substrate, and has a concave-convex structure. The concave-convex structure constituting the AG layer may be formed directly on the first main surface of the glass substrate, or may be formed on a layer different from the glass substrate. The AG layer may be, for example, a layer disposed on the first main surface of the glass substrate, in which particles having a given refractive index are dispersed, or may be a layer having a concave-convex structure on its surface.
[0105] In particular, the AG layer is preferably a layer having an uneven structure formed on at least a part of the surface itself of the AR layer opposite to the adhesive layer. The uneven structure that is formed on at least a part of the surface of the AR layer precursor film and that constitutes the AG layer can be formed, for example, by forming an AR layer precursor film on the surface of a transfer substrate having an uneven structure on its surface using the above-mentioned composition R, and then peeling the transfer substrate from the obtained AR layer precursor film.
[0106] The arithmetic mean height Ra of the uneven structure constituting the AG layer is preferably from 10 to 100 nm, and more preferably from 20 to 95 nm. The arithmetic mean height Ra of the uneven structure can be measured using a laser microscope "OLS4000" manufactured by Olympus Corporation. In this case, it is not necessary to form a concave-convex structure on the surface of the glass substrate and between the surface of the glass substrate and the adhesive layer. That is, the arithmetic mean height Ra of the surface of the glass substrate may be 10 nm or less.
[0107] (AFP layer) The AFP (Anti-Fingerprint) layer is an anti-fouling layer that has the function of suppressing the adhesion of various stains such as fingerprints, sweat, and dust, and making the stains less noticeable. The AFP layer is provided on the first main surface side of the glass substrate. The AFP layer 6 shown in Fig. 1 is disposed on the outermost surface of the cover glass 10. This allows the anti-fouling layer to fully exhibit its properties of keeping the display surface clean. The AFP layer is made of a fluorine-containing compound that can impart, for example, antifouling, water repellency, and oil repellency. The fluorine-containing compound is preferably a fluorine-containing organic compound (a compound having a fluorine-containing organic group). The fluorine-containing organic compound can be, for example, a fluorine-containing organic silicon compound.
[0108] <Colored area, open area> The cover glass may have a colored region formed by laminating a colored layer on the second main surface of the glass substrate. The cover glass may have an open region on the second main surface of the glass substrate. The open region refers to a region on the second main surface where no colored layer is laminated. The colored region is disposed, for example, in the peripheral portion of the second main surface. Here, the peripheral portion of the second main surface means a band-shaped region extending from the outer peripheral edge of the second main surface toward the center of the second main surface. The colored region may be disposed over the entire periphery of the peripheral portion of the second main surface. In this case, the opening region is the central region of the second main surface surrounded by the colored region. By arranging the colored regions and opening regions in this manner, in a display device having a cover glass, the display on the display is visible to a viewer through the opening, while components such as wiring members around the display are concealed by the colored layer so that they are not visible to the viewer. The shapes of the colored region and the open region are not limited to those described above, and may be appropriately selected depending on the shapes of the cover glass and the display, the image to be displayed on the display, and the like.
[0109] (colored layer) The colored layer is disposed on the second main surface, is a layer that constitutes a colored region, and contains at least a colorant.
[0110] When the cover glass is used in a display device, the colored layer can be used as a shielding layer (black layer) that shields components such as wiring circuits arranged on the periphery of the display from the viewer's field of vision, thereby improving the visibility and aesthetics of the display. The colored layer can also be used as a decorative layer having a pattern, letters, etc. that can be seen by an observer when observing through the glass substrate of the cover glass. By providing the cover glass with a colored layer that functions as such a decorative layer, the design of a display device and an article using the cover glass can be improved. The decorative layer can express, for example, various patterns such as wood grain, marble, metal, and pearl, as well as characters, images, marks, etc. These patterns can be freely designed depending on the application or installation location of the cover glass. The colored layer may have a multi-layer structure in which the decorative layer and the black layer are laminated in this order from the adhesive layer side.
[0111] The coloring agent contained in the coloring layer may be either a pigment or a dye, and a coloring agent of an appropriate color may be used depending on the purpose of the coloring layer. For example, when forming a coloring layer to be used as a light-shielding film, it is preferable to use a black coloring agent. When forming a pattern such as a wood grain pattern by the coloring layer, a plurality of coloring agents of different colors may be mixed and used to display a color other than black.
[0112] The colorant is preferably a pigment. In the black colored layer, it is preferable to use a black pigment as the colorant. Examples of black pigments include carbon black, titanium black, titanium carbon, iron oxide, titanium oxide, and graphite, with graphite or carbon black being preferred, and carbon black being more preferred. Colorants other than black include pigments and dyes that exhibit the respective colors.
[0113] The colorants may be used alone or in combination of two or more. The content of the colorant is preferably from 10 to 75% by mass, and more preferably from 15 to 70% by mass, based on the total amount of the color layer.
[0114] The colored layer may contain a component other than the colorant. Examples of the components other than the colorant contained in the colored layer include a curable resin, a curing agent, and additives such as a plasticizer, a non-volatile component, a release agent, an adhesive auxiliary, an antioxidant, and a dispersant. The colored layer preferably contains a cured resin. The cured resin contained in the colored layer may be a cured product of a curable resin and a curing agent, or may be a cured product (polycondensation product) obtained by reacting a curable resin with heat, light, acid, alkali, etc. The cured resin contained in the colored layer is preferably a cured product of a curable resin and a curing agent.
[0115] Examples of the curable resin contained in the colored layer include acrylic resin, polyester resin, epoxy resin, urethane resin, polyamide resin, phenol resin, and urea resin. Among them, a resin selected from the group consisting of acrylic resin, polyester resin, and epoxy resin is preferable.
[0116] The curing agent includes, for example, a heat curing agent and a light curing agent. The curing agent can be appropriately selected depending on the type of reactive group of the curable resin. The curing agent may be used alone or in combination of two or more. The colored layer may contain both a heat curing agent and a light curing agent. The content of the curing agent is appropriately adjusted depending on the content of the curable resin and the number of reactive groups, but is preferably 2 to 20% by mass, more preferably 2 to 10% by mass, based on the colored layer precursor described below. When it is in the above range, the scratch resistance of the colored layer can be improved, which is preferable.
[0117] The thickness of the colored layer is preferably 2 to 20 μm, more preferably 2 to 15 μm, even more preferably 2 to 13 μm, and even more preferably 2 to 10 μm. When the thickness of the colored layer is within the above range, the light blocking property or design property and the visibility can be improved in a well-balanced manner.
[0118] (Second adhesive layer) The colored region is preferably composed of only the colored layer, or composed of the colored layer and the second adhesive layer. In particular, in the colored region, a second adhesive layer may be disposed between the colored layer and the second main surface of the glass substrate. By providing a second adhesive layer between the second main surface of the glass substrate and the colored layer, a cover glass having a colored region that can accommodate a complex shape such as a complex curved shape of the glass substrate and has excellent adhesion can be obtained. In addition, in the colored region, it is preferable that no other layer is present between the colored layer or the second adhesive layer and the second main surface of the glass substrate.
[0119] The second adhesive layer preferably comprises a curable resin. The cured resin means a cured product obtained by curing a curable resin. The cured resin may be a cured product of a curable resin and a curing agent, or a cured product (polycondensation product) obtained by reacting a curable resin with heat, light, acid, alkali, or the like. The curable resin is preferably a cured product of a curable resin and a curing agent.
[0120] Examples of the curable resin contained in the second adhesive layer include acrylic resin, polyester resin, epoxy resin, urethane resin, polyamide resin, phenol resin, and urea resin. Among them, a resin selected from the group consisting of acrylic resin, polyester resin, and epoxy resin is preferable, and an acrylic resin is more preferable. The weight average molecular weight (Mw) of the curable resin used in the second adhesive layer is preferably from 10,000 to 80,000, and more preferably from 15,000 to 50,000.
[0121] Examples of the curing agent used in the second adhesive layer include a heat curing agent and a light curing agent. The curing agent can be selected appropriately depending on the type of reactive group possessed by the curable resin. The curing agent may be used alone or in combination of two or more types. The second adhesive layer may contain both a heat curing agent and a light curing agent.
[0122] The second adhesive layer preferably contains a cured resin as a main component. Here, "containing as a main component" means that the content of the cured resin is 50% by mass or more based on the total amount of the second adhesive layer. Alternatively, the content of the cured resin may be 100% by mass based on the total amount of the second adhesive layer.
[0123] The AG layer, AFP layer, and colored layer (colored region) described above are examples, and the configuration of each layer may be changed as appropriate within the scope of the function of each layer. In addition, the AG layer, AFP layer, and colored layer are not essential components of the cover glass, and some of the AG layer, AFP layer, and colored layer may not be provided depending on the configuration of the cover glass.
[0124] <Physical properties of cover glass> (Luminous reflectance) The luminous reflectance at a wavelength of 360 to 740 nm measured from the AR layer side of the cover glass is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less, in terms of better anti-reflection performance, reduced glare due to external light when used in a display, and better display characteristics and visibility. The luminous reflectance is, for example, 0.1% or more.
[0125] The luminous reflectance of the cover glass is a value obtained by measuring all reflected light, including specular reflected light, using a specular component include (SCI) method with a spectrophotometer. A more specific method for measuring the luminous reflectance will be described in the Examples section below.
[0126] (In-plane color difference of AR layer) When the first principal surface has regions with different radii of curvature, it is preferable that the region of the first principal surface where the AR layer is arranged satisfy the following requirement 1 in terms of better visibility of the display. Requirement 1: In the curved area of the first main surface where the AR layer is formed, three points are selected from the area with the smallest radius of curvature, and the L * Value, a * value and b * Measure the value and measure the L * Value, a * value and b * The arithmetic mean value of each of the values L * 1, a * 1 and b * In addition, among the areas on the first main surface where the AR layer is formed, three points are arbitrarily selected from the area with the largest radius of curvature, and L * Value, a * value and b * Measure the value and measure the L * Value, a * value and b * The arithmetic mean value of each of the values L * 2, a * 2 and b * 2 is calculated. Then, L * 1 and L * Difference from 2 ΔL * , a * 1 and a * Difference from 2 Δa * , and b * 1 and b * Difference from 2 Δb * The color difference ΔE calculated from the following formula (1) is 4 or less. * Value, a * value and b * The value is the L defined in JIS Z8781-4. * a * b * Lightness in color space L * , and chromaticity a * and b * means... ΔE={(ΔL * ) 2 +(Δa* ) 2 +(Δb * ) 2} 1 / 2 Formula (1)
[0127] The above ΔE is preferably equal to or less than 3, and more preferably equal to or less than 2. The above ΔE is, for example, equal to or more than 0.1. A more specific method for measuring the above ΔE will be described in the Examples below. The measurement conditions are preferably a reflection mode, a specular reflection treatment using the SCE method (specular reflection removed), and a measurement diameter of 3 mm. When a flat region on which the AR layer is formed is present on the first main surface, the region with the largest radius of curvature is the flat region, and when no flat region on which the AR layer is formed is present, the region with the largest radius of curvature is the curved region with the largest radius of curvature among the curved regions on which the AR layer is formed.
[0128] (Thickness difference between adhesive layer and AR layer) When the first main surface has regions with different radii of curvature, the difference ΔD between the total thickness of the adhesive layer and the antireflection layer in the region with the smallest radius of curvature and the total thickness of the adhesive layer and the antireflection layer in the region with the largest radius of curvature among the regions on the first main surface where the antireflection layer is disposed is preferably 75 nm or more. Furthermore, even if the difference ΔD in the total thickness is 75 nm or more, the cover glass in this embodiment more preferably satisfies the above requirement 1, and further preferably has a color difference ΔE of 3 or less, and particularly preferably has a color difference ΔE of 2 or less. The difference ΔD in the total thickness between the adhesive layer and the antireflection layer is determined by the difference between the arithmetic mean value D1 of the total thickness measured by selecting any three points from the area with the smallest radius of curvature in the curved area on which the antireflection layer is formed, and the average value D2 of the total thickness measured by selecting three points from the area with the largest radius of curvature. The total thickness of the adhesive layer and the antireflection layer can be measured by known methods, such as a method using a laser microscope or a method in which the cover glass is cut in the thickness direction at the measurement point and the cut surface is observed using a scanning electron microscope (SEM). It should be noted that the meaning of "the region with the largest radius of curvature" in the above ΔD is the same as that in the above ΔE.
[0129] [Cover glass manufacturing method] The method for manufacturing the cover glass may be any method capable of forming an adhesive layer and an AR layer on the first main surface of a glass substrate having a first main surface and a second main surface, at least a portion of which is a curved region. Examples of the method for producing the cover glass include a method in which an adhesive layer and an AR layer are formed on the first main surface of the glass base by a transfer decoration method using a transfer member having an adhesive layer and an AR layer.
[0130] A more specific method for producing a cover glass by the transfer decoration method is as follows. First, a glass substrate having a first main surface and a second main surface, at least a part of which is a curved region, is prepared. Next, a transfer member having a transfer substrate, an AR layer precursor film, and an adhesive film in this order is prepared. Next, the transfer member is laminated on the glass substrate so that the first main surface of the glass substrate and the adhesive film are in contact with each other. Next, the adhesive film and the anti-reflection layer precursor film (hereinafter also referred to as "AR layer precursor film") are cured to produce a laminate including an adhesive layer disposed on the first main surface of the glass substrate and an AR layer disposed on the adhesive layer.
[0131] In a method for producing a cover glass having an adhesive layer and an AR layer on the main surface of a glass substrate, at least a portion of which is curved, a transfer decoration method is adopted and further combined with the use of a transfer member having an AR layer precursor film and an adhesive film, in that order, on a transfer substrate, so that a cover glass can be produced that is compatible with complex shapes, such as a complex curved shape, of the glass substrate and has an AR layer that has excellent surface hardness and adhesion to the curved region on the main surface of the glass substrate.
[0132] The method for producing a cover glass by the transfer decoration method will be described in detail below.
[0133] <Preparation of glass substrate> The glass substrate is produced, for example, by processes such as cutting, milling, polishing and shaping a large-sized sheet glass.
[0134] Examples of methods for cutting the plate glass include cutting with a diamond blade, scribe breaking, laser cutting, and chemical cutting by etching. For cutting or polishing, a grindstone may be used, or a buff or brush made of cloth, leather, rubber, or the like other than the grindstone may be used. In this case, an abrasive such as cerium oxide, alumina, carborundum, or colloidal silica may be used. Among these, a grindstone is preferable as the polishing tool from the viewpoint of dimensional stability.
[0135] A glass substrate having at least a partially curved surface region can be produced, for example, by heating a flat glass sheet to soften it and curve at least a portion of the glass sheet. The above-mentioned flat plate glass forming method may be, for example, a known forming method such as gravity forming method, vacuum forming method, and press forming method. According to the shape of the glass base after forming, a known forming method is appropriately selected, and a flat plate glass is formed by the selected forming method, thereby producing a glass base having at least a part of a curved surface region. According to the shape of the glass plate after forming, two or more forming methods may be used in combination. For a method for forming a glass substrate having a curved surface, reference can be made to paragraphs
[0044] to
[0048] of WO 2016 / 125713.
[0136] In order to improve the strength of the glass base, it is preferable to subject the glass member obtained by the above steps to a chemical strengthening treatment. The method of chemical strengthening treatment is as described above.
[0137] <Preparation of transfer material> Separately from the preparation of the glass substrate, a transfer member having a transfer substrate, an AR layer precursor film, and an adhesive film in this order is prepared. The transfer member can be prepared, for example, by the following method. First, a coating film is formed on the surface of a transfer substrate using the above composition R, and the coating film is dried as necessary to produce a multilayer body having a transfer substrate and an AR layer precursor film disposed on the surface of the transfer substrate. Next, a coating film is formed on the surface of the formed AR layer precursor film using the above composition B, and the coating film is dried as necessary to produce a transfer member having a transfer substrate, an AR layer precursor film disposed on the surface of the transfer substrate, and an adhesive film disposed on the surface of the AR layer precursor film.
[0138] (Transfer substrate) The transfer substrate is appropriately selected depending on the method for forming the AR layer precursor film, the method for forming the adhesive film, and the method for transferring to the glass substrate. As the transfer substrate, a resin substrate is preferable in terms of flexibility, heat resistance, surface cleanliness, and smoothness. Examples of the resin constituting the transfer substrate include thermoplastic resins such as polyethylene terephthalate resin, polyethylene resin, and polypropylene resin. Depending on the purpose of facilitating peeling after transfer, a functional layer may be provided on the surface of the transfer substrate, and the surface of the transfer substrate may be subjected to a surface treatment such as an easy-adhesion treatment and a corona treatment.
[0139] The thickness of the transfer substrate is, for example, 10 to 300 μm, preferably 20 to 250 μm, and more preferably 40 to 200 μm. In addition, when the transfer substrate is softened when the transfer member is laminated on the glass substrate as described below, the glass transition point (Tg) of the resin constituting the transfer substrate is preferably 70 to 180°C, more preferably 100 to 150°C.
[0140] The composition R used to form the AR layer precursor film and the composition B used to form the adhesive film are as already explained as the AR layer-forming composition R and the adhesive layer-forming composition B, respectively.
[0141] Composition R and composition B can be prepared by a known method. Composition R and composition B may be prepared by mixing the components contained in each composition, or a preliminary composition may be prepared by mixing two or more of the above components, and then the preliminary composition may be mixed with other components or other preliminary compositions to prepare the target composition.
[0142] (Formation of AR layer precursor film) As a method for forming a coating film of composition R on the surface of a transfer substrate using composition R, a known coating film forming method can be applied, and examples thereof include screen printing, inkjet printing, offset printing, flexographic printing, stencil printing, gravure printing, roller printing, curtain flow, die coating, gravure coating, microgravure coating, reverse coating, roll coating, flow coating, and spray coating.
[0143] When the composition R contains a solvent, it is preferable to dry the coating film to evaporate the solvent. The coating film can be dried by a known method such as heating the coating film.
[0144] When the composition R contains a refractive index lowering component and a curable resin, the AR layer precursor film may contain the refractive index lowering component and the curable resin before curing, or may contain the refractive index lowering component and a cured resin (a cured product of the curable resin). When the AR layer precursor film of the transfer member contains the refractive index lowering component and the curable resin before curing, the AR layer is formed by transferring the adhesive layer and the AR layer precursor film to the glass substrate using the transfer member, or by performing a curing process on the AR layer precursor film simultaneously with the transfer. On the other hand, the AR layer precursor film containing the refractive index lowering component and the curable resin is formed by curing a coating of the composition R containing the refractive index lowering component and the curable resin.
[0145] The thickness of the AR layer precursor film in the transfer member, including the preferred embodiment, may be the same as the thickness of the AR layer described above.
[0146] (Adhesive film formation) The method for forming a coating film of composition B on the surface of the AR layer precursor film using composition B can be carried out in accordance with the method for forming a coating film of composition R, except for the matters described below.
[0147] When composition B contains a solvent, it is preferable to evaporate the solvent by drying the coating film of composition B. For drying the coating film, a known method such as heating the coating film can be applied. The heat treatment is carried out under conditions that do not affect the performance of the adhesive layer. The heat treatment conditions may be appropriately set according to the composition of composition B. The heat treatment temperature may be 90°C or higher and 200°C or lower. The heat treatment time may be 10 seconds or higher and 10 minutes or lower. A coating of Composition B may be used as an adhesive film without drying.
[0148] Methods for forming the adhesive film include a method for forming an adhesive film of a single layer structure using the above composition B1, and a method for forming an adhesive film of a multilayer structure using the above compositions B2 and B3. Of these, it is preferable to form an adhesive film having a single layer structure using composition B1, since it requires fewer steps such as coating and drying of the composition, and it has better adhesion to curved areas.
[0149] The thickness of the adhesive film in the transfer member, including the preferred embodiment, may be the same as the thickness of the adhesive layer described above.
[0150] As a method for preparing a transfer member other than the above, the following method can also be mentioned. First, a coating film is formed on the surface of the first transfer substrate using the composition B, and the coating film is dried as necessary to produce a first multilayer body having a first transfer substrate and an adhesive film disposed on the surface of the first transfer substrate. Next, a coating film is formed on the surface of a second transfer substrate different from the first transfer substrate using the composition R, and the coating film is dried as necessary to produce a second multilayer body having a second transfer substrate and an AR layer precursor film disposed on the surface of the second transfer substrate. Next, the first transfer substrate and the second transfer substrate are bonded together so that the adhesive film and the AR layer precursor film are in contact with each other, to produce a transfer member having the first transfer substrate, adhesive film, AR layer precursor film, and second transfer substrate in this order.
[0151] The formation of the adhesive film on the surface of the first transfer substrate and the formation of the AR layer precursor film on the surface of the second transfer substrate are carried out in accordance with the method already described.
[0152] The first transfer substrate and the second transfer substrate can be bonded together by a known technique. For example, a method of manufacturing a transfer member includes a method of bonding the first transfer substrate and the second transfer substrate together by roll-to-roll processing using a laminator while unwinding the first multilayer body and the second multilayer body, at least one of which is wound into a roll after production.
[0153] The lamination is preferably performed while applying pressure. The pressure may be, for example, 0.1 to 50 N / cm, and preferably 0.5 to 30 N / cm. The temperature during lamination may be 0 to 40° C. The temperature during lamination is preferably 10° C. or higher, more preferably 15° C. or higher. The temperature during lamination is preferably 35° C. or lower, more preferably 30° C. or lower. The transfer member after lamination may be heated. Heating after lamination further improves the adhesion between the adhesive film and the AR layer precursor film.
[0154] The transfer member having the first transfer substrate, adhesive film, AR layer precursor film and second transfer substrate in this order obtained by the above method is used to prepare a cover glass after peeling off the first transfer substrate.
[0155] <Lamination of transfer materials> Next, using the transfer member prepared by the above method, the transfer member is laminated onto the glass substrate so that the first main surface of the glass substrate and the adhesive film of the transfer member are in contact with each other.
[0156] When laminating the transfer member on the glass substrate, the transfer member before lamination may be heated to laminate the transfer member having the softened transfer substrate, the AR layer precursor film, and the adhesive film on the glass substrate. By laminating the softened transfer substrate, the mutual adhesion between the glass substrate, the adhesive layer, and the AR layer is further improved, and an AR layer having excellent adhesion can be more easily formed on a glass substrate in which at least a part of the first main surface is a curved region. When laminating the transfer member onto the glass substrate, the glass substrate may be heated prior to lamination.
[0157] The heating temperature of the transfer member before lamination is, for example, 80 to 180°C, and preferably 100 to 160°C. When at least one of the AR layer precursor film and the adhesive film contains a heat curing agent, the heating temperature of the transfer member before lamination may be equal to or higher than the curing temperature of the heat curing agent, and can be adjusted depending on whether or not a post-curing treatment described later is performed and the embodiment. The transfer member can be heated by, for example, infrared radiation, superheated steam, or contact with a hot plate. The glass substrate can also be heated in a similar manner.
[0158] The glass substrate and the transfer member are preferably laminated by a vacuum / pressure molding method. More specifically, the method involves placing the prepared glass substrate and transfer member in a chamber so that a first main surface of the glass substrate faces the adhesive film, dividing the chamber into a first space containing the glass substrate and a second space not containing the glass substrate by the transfer member, heating and softening the transfer substrate, and reducing the air pressure in the first space below the air pressure in the second space, thereby bringing the adhesive film into contact with the main surface of the glass substrate. When the glass substrate and the transfer member are laminated by the above-mentioned method, the softened transfer member deforms along the first main surface (including the curved area) of the glass substrate, resulting in better adhesion between the bonded adhesive film (adhesive layer) and the first main surface.
[0159] The heating temperature and heating method of the transfer substrate in the vacuum pressure molding method are as described above. As a heating method of the transfer substrate, a method of bringing the transfer substrate into contact with a hot plate arranged to face the transfer substrate in the second space of the vacuum pressure molding machine is preferable. When laminating the glass substrate and the transfer member by vacuum and pressure molding, the glass substrate may be heated.
[0160] As a method for making the air pressure in the first space (glass substrate side) lower than that in the second space, a method for reducing the pressure in the first space is preferable, and a method for reducing the pressure in the first space and simultaneously pressurizing the second space is more preferable. The air pressure in the first space when the adhesive film is brought into contact with the first main surface of the glass substrate is, for example, 0.1 MPa or less, and preferably 0.05 MPa or less. The air pressure in the first space is preferably 10 Pa or more. When the second space is pressurized, the air pressure in the second space is, for example, 0.1 MPa or more, preferably 0.2 MPa or more, and preferably less than 1 MPa. For details of the lamination method of the glass substrate and the transfer member by the vacuum pressure molding method, a known method can be referred to.
[0161] <Post-curing treatment> After laminating the transfer member on the glass substrate to produce a laminate, a post-curing treatment may be performed. The presence or absence of a post-curing treatment is appropriately selected depending on the components constituting the adhesive film and the components constituting the AR layer precursor film. For example, when at least one of the composition R and the composition B contains at least one of a thermal polymerization initiator and a photopolymerization initiator, and at least one of the AR layer precursor film and the adhesive film in the laminate is a thermosetting or active energy ray curable film, it is preferable to perform a post-curing treatment.
[0162] When at least one of the composition R and the composition B contains a photopolymerization initiator, it is preferable to irradiate active energy rays such as ultraviolet rays (hereinafter also referred to as "light irradiation") as a post-curing treatment to cure the laminated AR layer precursor film and adhesive film. In curing the adhesive film or the AR layer precursor film by light irradiation, the wavelength, irradiation amount, irradiation time, etc. of the irradiated light are appropriately selected depending on the type of photopolymerization initiator and the composition of the film containing the photopolymerization initiator, and are, for example, 0.3 to 30 mW / cm 2 One method is to irradiate the area with ultraviolet light of about 1 to 30 minutes.
[0163] When at least one of composition R and composition B contains a thermal polymerization initiator, the laminate may be subjected to a heat treatment as a post-curing treatment in order to cure the laminated AR layer precursor film and adhesive film. The heating temperature in the heat treatment is preferably at least 10° C. higher than the curing temperature of the thermal polymerization initiator. The heating temperature and heating time are appropriately selected depending on the type of thermal polymerization initiator and the composition of the film containing the thermal polymerization initiator.
[0164] When producing a cover glass by the above-mentioned transfer decoration method, the transfer base material may be used as a protective member without being peeled off, but is usually peeled off. When the post-curing treatment is performed, the transfer substrate may be peeled off before or after the post-curing treatment. In order to obtain a better adhesion between the adhesive layer and the main surface of the glass substrate, it is preferable to peel off the transfer substrate after the post-curing treatment. When laminating the glass substrate and the transfer member by vacuum pressure molding, post-curing treatment and peeling of the transfer base material from the cover glass may be performed in the apparatus in which vacuum pressure molding is performed.
[0165] By the above method, a cover glass is produced in which a glass substrate, an adhesive layer, and an AR layer are laminated in this order.
[0166] A cover glass having an AG layer disposed on the first main surface side of a glass substrate is produced by carrying out a step of forming an AG layer at any stage of the above-mentioned cover glass manufacturing process or after the manufacture of the cover glass. The method for forming the AG layer is appropriately selected from known methods. Among them, in the above-mentioned method for producing a cover glass by the transfer decoration method, a method for forming the AG layer by using a transfer substrate having an uneven structure on the surface on the side in contact with the AR layer precursor film is preferred. Specifically, in the preparation step of the transfer member having the above-mentioned transfer substrate, AR layer precursor film, and adhesive film in this order, it is preferred to form an AR layer precursor film on the uneven structure-having surface of the transfer substrate (or the second transfer substrate) using the composition R, prepare the transfer member, laminate the obtained transfer member on a glass substrate, and then peel off the transfer substrate from the laminate to provide an AG layer consisting of the uneven structure formed on the visible surface of the AR layer. The uneven structure formed on the surface of the transfer substrate can be formed based on known techniques, and its shape and size are appropriately selected so that the uneven structure transferred to the surface of the AR layer can exhibit the desired antiglare properties.
[0167] A cover glass having an AFP layer disposed on the AR layer is produced by carrying out a step of forming the AFP layer after the production of the cover glass. The production method of the AFP layer is appropriately selected from known methods.
[0168] A cover glass having a colored region and an open region on the second major surface of a glass substrate is obtained by forming a colored layer and an optional second adhesive layer on the second major surface of the glass substrate at any stage after the glass substrate is prepared. The step of forming the colored region having the colored layer and the optional second adhesive layer can be performed at any time. For example, the colored region may be formed on the glass substrate before laminating the transfer member, or the colored region may be formed after producing the cover glass having the adhesive layer and the AR layer. The method for producing each of the colored layer and the second adhesive layer is appropriately selected from known methods.
[0169] The cover glass of the present invention can be used as a cover glass for a display device, and can protect an object while ensuring the visibility of a displayed image on the display.
[0170] [Display device] One embodiment of the display device of the present invention is a display device including the cover glass of the present invention and a display. The cover glass of the present invention laminated on the display is arranged, for example, so that the second main surface side of the glass base faces the display. The display device may be, for example, an in-vehicle display device that is mounted on a vehicle and used in the vehicle. The in-vehicle display device may be, for example, a car navigation device, a meter panel, or a rear seat entertainment (RSE) device that allows passengers in the rear seats to watch videos and the like.
[0171] The on-vehicle display device will be described in more detail below. The in-vehicle display device includes, for example, the cover glass of the present invention, a housing, a display, and an adhesive layer.
[0172] The in-vehicle display device has a housing that houses each of the components. A display is disposed inside the housing. Examples of the display include a liquid crystal panel, an organic EL (electroluminescence) panel, and an electronic ink type panel. The display may have a touch panel, etc. Images of, for example, a car navigation screen, various meters such as a speedometer, and a start button are displayed on the display.
[0173] The adhesive layer bonds the cover glass to the display in the in-vehicle display device, so that the cover glass functions as a cover glass for the display. The adhesive layer may be, for example, a layer made of a transparent resin obtained by curing a liquid curable resin-containing composition. The adhesive layer may be an OCA (Optical Clear Adhesive) film or tape. The thickness of the adhesive layer is preferably 5 μm or more, more preferably 50 μm or more. On the other hand, the thickness of the adhesive layer is preferably 400 μm or less, more preferably 200 μm or less.
[0174] In addition to the above-mentioned in-vehicle display devices, examples of display devices to which the display device having the cover glass of the present invention can be applied include panel displays (liquid crystal displays, organic EL displays, etc.) and display devices of mobile devices, etc. EXAMPLES
[0175] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following examples. Examples 1 to 7 are examples, and Examples 8 to 11 are comparative examples.
[0176] [Preparation of Adhesive Layer-Forming Composition] The raw materials shown below were mixed and stirred using a planetary centrifugal mixer to prepare composition B used to form the adhesive layer in each example. Reactive acrylic resin: Daicel-Allnex Corporation "KRM-9322" - Multifunctional urethane acrylate: Daicel-Allnex Corporation "KRM-8452" Reactive silsesquioxane: A silsesquioxane compound having an acryloyloxy group at the end ("AC-SQ TA-100" manufactured by Toagosei Co., Ltd.) Dispersion of silica particles: Dispersion of colloidal silica with acryloyloxy groups on the surface in methyl ethyl ketone (Nissan Chemical Industries, Ltd.'s "MEK-AC-2140Z", solid content concentration 45.7% by mass) Photoinitiator: BASF's "Omnirad (registered trademark) 184" Silane coupling agent F: A silane coupling agent having an acryloyloxy group ("KBM-5103" manufactured by Shin-Etsu Chemical Co., Ltd.) Dilution solvent: 2-butanone (Kanto Chemical Co., Ltd.)
[0177] When preparing composition B, the raw materials other than the dilution solvent were added in the amounts shown in Table 1 described below, and the amount of the dilution solvent added was adjusted so that the solids concentration of composition B would be the value shown in the "Solids concentration (mass%)" column in Table 1 described below. For example, the composition B-1 used in Example 1 was prepared by mixing 43.5 parts by mass of the reactive acrylic resin, 12.4 parts by mass of the polyfunctional urethane acrylate, 35.1 parts by mass of the silica particle dispersion, 4.0 parts by mass of the photoinitiator, 5.0 parts by mass of silane coupling agent F, and an amount of 2-butanone as a dilution solvent such that the solid content concentration of the prepared composition B-1 was 30% by mass.
[0178] Table 1 described later shows the compositions B-1 to B-8. In the table, the columns "reactive acrylic resin," "multifunctional urethane acrylate," "reactive silsesquioxane," "silica particle dispersion," "photoinitiator," and "silane coupling agent F" indicate the amount of each component used in preparing each composition (unit: parts by mass).
[0179] [Preparation of primer layer forming composition] The raw materials shown below were mixed and stirred using a planetary centrifugal mixer to prepare composition b used for forming a primer layer. Silane coupling agent G: A silane coupling agent having an acryloyloxy group ("KBM-5103" manufactured by Shin-Etsu Chemical Co., Ltd.) Silane coupling agent H: A silane coupling agent that does not have an ethylenically unsaturated group ("KBM-3066" manufactured by Shin-Etsu Chemical Co., Ltd., 1,6-bis(trimethoxysilyl)hexane) Water: Distilled water (manufactured by Junsei Chemical Co., Ltd.) 10% nitric acid: A diluted solution obtained by diluting concentrated nitric acid (manufactured by Kanto Chemical Co., Ltd., concentration 60% by mass) with distilled water (manufactured by Junsei Chemical Co., Ltd.) six times by weight. Dilution solvent: Ethanol (Kanto Chemical Co., Ltd.)
[0180] When preparing each composition, the raw materials other than the dilution solvent were added in the amounts shown in Table 1 described below, and the amount of the dilution solvent added was adjusted so that the solid content concentration of composition b would be the value shown in the "Solid content concentration (mass%)" column in Table 1 described below. For example, the composition b-1 used in Example 6 was prepared by mixing 65.0 parts by mass of silane coupling agent G, 33.4 parts by mass of water, 1.6 parts by mass of 10% nitric acid, and an amount of ethanol as a dilution solvent such that the solid content concentration of the prepared composition b-1 was 1.2% by mass.
[0181] The compositions of primer compositions b-1 and b-2 are shown in Table 1 below. In the table, the columns "Silane coupling agent G," "Silane coupling agent H," "Water," and "0% Nitric Acid" indicate the amount of each component used in preparing each composition (unit: parts by mass).
[0182] [Preparation of AR layer forming composition] Composition R used to form the AR layer in each example was prepared by the following method. 24.8 parts by mass of reactive acrylic resin ("KRM-9322" manufactured by Daicel-Allnex Corporation), 13.3 parts by mass of multifunctional urethane acrylate ("KRM-8452" manufactured by Daicel-Allnex Corporation), 13.3 parts by mass of multifunctional silicone acrylate oligomer containing fluorine atoms ("Shikoh (trademark) UV-AF305" manufactured by Mitsubishi Chemical Corporation), and 4.8 parts by mass of a photoinitiator (BASF Ltd.'s "Omnirad (registered trademark) 184") was mixed in. Furthermore, 43.8 parts by mass of a hollow silica particle dispersion (refractive index reduced particles, JGC Catalysts and Chemicals Ltd.'s "Surulia 4320", solid content concentration 20.7% by mass) was blended into the mixture. The resulting mixture was diluted with propylene glycol monomethyl ether until the solid content concentration became 2% by mass, to obtain a transparent composition R-1.
[0183] [Example 1] <Preparation of transfer member 1> As a first transfer substrate, a substrate 1 ("TP-03" manufactured by PANAC Corporation, thickness 50 μm) made of polyethylene terephthalate that had been subjected to a release treatment was prepared. Composition B-1 was applied to the release-treated surface of the substrate 1 using a No. 8 bar coater in an amount that would result in a layer thickness of 3 μm after drying. The mixture was then dried at 60° C. for 5 minutes to volatilize the solvent and form an uncured adhesive film.
[0184] As a second transfer substrate, a substrate 2 made of a non-stretched polypropylene film ("XET-20" manufactured by Okamoto Corporation, thickness 150 μm) was prepared. A gravure coater was used to apply the composition R-1 to the surface of the substrate 2 in an amount that would result in a layer thickness of 90 nm after drying. The composition was then dried at 80°C for 1 minute to volatilize the solvent, forming an uncured AR layer precursor film. The substrate 2 on which the AR layer precursor film was formed was wound into a roll.
[0185] While unwinding the substrate 2 wound into a roll, the surface of the adhesive film supported by the substrate 1 and the surface of the AR layer precursor film supported by the substrate 2 were bonded together. The bonding was performed under a pressure of 20 N / cm and at a temperature of 25° C. In this way, a transfer member 1 having the substrate 1, the adhesive film, the AR layer precursor film, and the substrate 2 in this order was produced.
[0186] The thickness of the adhesive film on the transfer member 1 was measured by the following method. The average thickness of the adhesive film measured by the above method was 3 μm. The average thickness of the adhesive film measured can be said to be equal to the thickness of the adhesive layer of the produced cover glass.
[0187] <Preparation of glass substrate> A rectangular aluminosilicate glass ("Dragon Trail (registered trademark)" manufactured by AGC Inc.) having a thickness of 1.3 mm, a length of 100 mm and a width of 200 mm was prepared as a flat plate glass. A flat glass plate was curved by hot forming to produce a glass substrate having a flat region and a curved region. The obtained glass substrate has a rectangular flat area of 100 mm in length and 150 mm in width, and a curved area of 100 mm in length and 50 mm in width adjacent to the flat area in a plan view. The curved area is curved only in the horizontal direction (the longitudinal direction of the glass sheet), and the first radius of curvature R of the curved area is 1 was 1500mm. In the produced glass base, the principal surface on the outer diameter side of the curved region was designated as a first principal surface, and the principal surface on the inner diameter side of the curved region was designated as a second principal surface.
[0188] <Manufacturing cover glass by transfer decoration method> A glass substrate was placed on a placement table provided in the chamber of a vacuum pressure forming machine so that the first main surface faced vertically upward. Next, the base material 1 was peeled off from the transfer member 1, and the transfer member 1 from which the base material 1 had been peeled off was placed above the glass substrate so that the adhesive film faced the first main surface of the glass substrate. After the base material 2 was heated to 130°C using a preheating plate, the placement table was moved upward to bring the heated adhesive film into contact with the first main surface of the glass substrate. Next, the air pressure in the first space containing the glass substrate in the chamber was reduced to about 400 Pa.
[0189] After the pressure in the first space was returned to atmospheric pressure, the laminate consisting of the glass substrate, the adhesive film, the AR layer precursor film and the base material 2 was removed from the chamber of the vacuum and pressure forming machine, and the base material 2 was peeled off from the laminate. This laminate was heated in an oven at 120° C. for 10 minutes, then the laminate was taken out and allowed to cool to room temperature. The laminate was placed on a placement table installed in a UV-LED exposure machine so that the first main surface faced vertically upward. Next, a UV-LED lamp was installed so as to face the first main surface of the laminate, and an integrated light amount of 2000 mJ / cm 2 was applied. 2 More than 1000 nm of UV radiation was applied. Through the above steps, a cover glass was manufactured that had a glass substrate, an adhesive layer disposed on the first main surface of the glass substrate, and an AR layer disposed on the adhesive layer.
[0190] [Example 2 to Example 5] The cover glasses of Examples 2 to 5 were produced according to the method described in Example 1, except that Compositions B-2 to B-5 were used instead of Composition B-1 used in Example 1, respectively.
[0191] [Example 6] A transfer member 6 having a substrate 1, an adhesive film, an AR layer precursor film, and a substrate 2 in this order was produced according to the method described in Example 1, except that the composition B-6 was used instead of the composition B-1 used in Example 1. The glass substrate prepared in Example 1 was stood vertically with the curved region positioned above the flat region, and composition b-1 was poured along the upper edge from the first main surface side of the glass substrate at a distance of 10 mm from the upper end of the curved region of the glass substrate to apply composition b-1 to the first main surface (convex surface) of the glass substrate, and then heated at 120°C for 30 minutes in an air atmosphere to obtain glass substrate 1 having a primer layer.
[0192] Next, the cover glass of Example 6 was produced according to the method described in Example 1 using the glass substrate 1 having the obtained primer layer.
[0193] [Example 7] The transfer member of Example 7 was produced according to the method described in Example 6, except that the composition b-2 was used as the primer layer-forming composition.
[0194] [Example 8] As a transfer substrate, "DECOFIT (registered trademark) Q01CK" manufactured by Toray Industries, Inc., glass transition temperature Tg: approximately 70° C. was prepared. A metal oxide layer was formed on the surface of the transfer substrate by sputtering as an AR layer precursor film. In the film formation, the conditions were adjusted so that the components and raw materials of each layer and the thickness of each layer were as shown in Table A below so that the metal oxide layer would function as an anti-reflection layer. Note that the metal oxide layers shown in the table were formed in the order of the first layer, the second layer, the third layer, and the fourth layer from the side closest to the transfer substrate.
[0195] [Table 1]
[0196] Next, the release-treated surface of the substrate 1 ("TP-03" manufactured by PANAC Corporation, thickness 50 μm) made of polyethylene terephthalate similarly to Example 1 was coated with a No. 8 bar coater with Composition B-7 in an amount that would result in a layer thickness of 3 μm after drying. The coating was then dried at 60° C. for 5 minutes to volatilize the solvent and form an uncured adhesive film. As in Example 1, the surface of the adhesive film supported by the substrate 1 and the surface of the AR layer precursor film supported by the substrate 2 were bonded together while the substrate 2 wound into a roll was unwound. The bonding was performed under a pressure of 20 N / cm and at a temperature of 25° C. In this way, a transfer member having the substrate 1, the adhesive film, the AR layer precursor film, and the substrate 2 in this order was produced.
[0197] An attempt was made to manufacture a cover glass using a vacuum / compressed air molding machine in accordance with the method described in Example 1, except that the transfer member obtained above was used and the molding temperature was set to 100°C. However, when the glass substrate and the transfer member were laminated by vacuum molding, cracks occurred in the AR layer precursor film in the curved region of the glass substrate, and the AR layer precursor film could not be transferred to the glass substrate.
[0198] Therefore, in order to carry out the evaluation tests of luminous reflectance and pencil hardness described below, a cover glass for evaluation was prepared by the following method. A flat glass sheet before being curved by heat forming was placed on a placement table provided in a chamber of a vacuum pressure forming machine. Next, a transfer member 8 was placed above the glass sheet so that the adhesive film faced the glass sheet. Except for placing the glass sheet and the transfer member 8 in this manner, a cover glass for evaluation of Example 8 having a flat glass substrate, an adhesive layer, and a sputtered layer (AR layer) in this order was produced according to the method described in Example 1.
[0199] [Examples 9 and 10] The cover glasses of Examples 9 and 10 were produced according to the method described in Example 1, except that compositions B-6 and B-8 were used instead of composition B-1 used in Example 1, and the laminate was not irradiated with UV light.
[0200] [Example 11] 2-Butanone was added to a polyester adhesive ("GM-3TR" manufactured by Jujo Chemical Co., Ltd.) to prepare a composition for forming an adhesive layer (composition B-9) having a solid content of 30% by mass. The cover glass of Example 11 was produced according to the method described in Example 1, except that composition B-9 was used instead of composition B-1 used in Example 1, and the laminate was not irradiated with UV light.
[0201] [evaluation] The cover glass and the like of each example were subjected to the following evaluations. The evaluation results are shown in Table 1 below.
[0202] <Luminous reflectance> An evaluation sample was prepared by attaching a black sheet with adhesive (product name: Kukiri Miel, manufactured by Tomoegawa Paper Co., Ltd.) to the surface of the glass substrate opposite to the adhesive layer and the AR layer. The luminous reflectance of the evaluation sample was measured from the surface on the AR layer side by the SCI method. The measurement was performed in the measurement wavelength range of 360 to 740 nm using a spectrophotometer "CM-5" (manufactured by Konica Minolta, Inc.).
[0203] <Measurement of color difference ΔE> A spectrophotometer ("CM-5" manufactured by Konica Minolta, Inc.) was used as the measuring device to obtain the spectral reflectance of the area on the first principal surface where the AR layer was disposed, and the color difference ΔE between the curved area on which the AR layer was formed and the flat area on which the AR layer was formed was measured. First, the cover glass was placed on the stage with the second main surface of the glass substrate facing downward, and the spectral reflectance of the first main surface was measured. The measurement conditions for the above measurement were reflection mode, specular reflection treatment was SCE method (specular reflection removal), and the measurement diameter was 3 mm. Three points were selected from the curved surface area on which the AR layer was formed, and the L * Value, a * value and b * Measure the value and measure the L * Value, a * value and b * The arithmetic mean value of each of the values L * 1, a * 1 and b * Next, three points were selected from the planar area on which the AR layer was formed, and the L * Value, a* value and b * Measure the value and measure the L * Value, a * value and b * The arithmetic mean value of each of the values L * 2, a * 2 and b * 2 was calculated. Next, L * 1 and L * Difference from 2 ΔL * , a * 1 and a * Difference from 2 Δa * , and b * 1 and b * Difference from 2 Δb * The color difference ΔE was calculated using the following formula (1). ΔE={(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 Formula (1)
[0204] The measurement results of the color difference ΔE of each cover film are shown in the "ΔE" column of Table 1. In the "ΔE" column, when the color difference ΔE was 4 or less, "○" was recorded, and when the color difference ΔE was more than 4, "×" was recorded. In Example 10, the AR layer was peeled off from the first main surface of the glass substrate, and the color difference ΔE could not be measured, so in Table 1, the "ΔE" column for Example 10 is entered as "-".
[0205] <Measurement of the difference in total thickness ΔD> Using a laser microscope as a measuring device, three arbitrary points were selected from the curved area where the AR layer was formed, the total thickness of the adhesive layer and the AR layer were measured, and the total thickness D1 was obtained by arithmetically averaging the obtained measurements. Similarly, three arbitrary points were selected from the flat area where the AR layer was formed, the total thickness of the adhesive layer and the AR layer were measured, and the total thickness D2 was obtained by arithmetically averaging the obtained measurements. Next, the difference ΔD between D1 and D2 was calculated. The measurement results of the difference ΔD in the total thickness of each cover film are shown in the "ΔD" column of Table 1. In the "ΔD" column, when the difference ΔD in the total thickness was 75 μm or more, "○" was recorded, and when the difference ΔD in the total thickness was less than 75 μm, "×" was recorded. In Example 10, the AR layer was peeled off from the first main surface of the glass substrate, and the difference in total thickness ΔD could not be measured, so in Table 1, the column for "ΔD" for Example 10 shows "-".
[0206] <Glass adhesion> The adhesion of the AR layer to the glass substrate was evaluated by carrying out a cross-cut test according to JIS K5600-5-6. More specifically, the AR layer disposed on the flat area of the glass substrate was cut into a lattice shape with a width of 1 mm to form 100 squares. Cellophane tape was attached to the area of the AR layer where the squares were formed, and then peeled off. After the cellophane tape was peeled off, the squares were observed, and the adhesion of the AR layer to glass was evaluated based on the observation results and in accordance with the following criteria. When the cross-cut test results in an evaluation of ◯, the cover glass can be said to have better adhesion of the AR layer formed on the glass substrate having a curved region. In Example 10, the AR layer was peeled off from the first main surface of the glass substrate, so that the glass adhesion evaluation could not be performed. In Table 1 described later, the glass adhesion evaluation of Example 10 is marked with "-".
[0207] (Glass adhesion evaluation criteria) ○: No peeling of the AR layer was observed before the cross-cut test. After the cross-cut test, no peeling was observed in any of the squares, or only small peeling was observed at the intersections of the cuts, and the ratio of the area of the peeled region to the total area of the AR layer was 5% or less. △: No peeling of the AR layer was observed before the cross-cut test, but partial peeling was observed after the cross-cut test at the intersections of the cuts and / or along the cut lines, etc. The ratio of the area of the peeled regions to the total area of the AR layer was more than 5%.
[0208] <Pencil hardness> On the surface where the AR layer of the cover glass of each example was exposed, a pencil hardness test was carried out in accordance with JIS K5600-5-4. More specifically, the pencil hardness of the AR layer surface was measured using a load fluctuation type friction and wear tester "HHS-2000" (manufactured by Shin-Toyo Kagaku Co., Ltd.) and a pencil for scratch hardness test (manufactured by Mitsubishi Pencil Co., Ltd.). Table 1 described later shows the measurement results of the pencil hardness. In Table 1, "<H" means that scratches or defects occurred on the surface of the AR layer even by the pencil hardness test using a pencil with hardness H.
[0209] <Transferability> In the step of laminating the glass substrate and the transfer member by the transfer decoration method, after peeling the base material 2 from the laminate, the state of the laminate and the AR layer precursor film before heating in the oven was observed. Based on the observation results, the transferability was evaluated according to the following criteria. (Transferability evaluation criteria) ○: All of the AR layer precursor film is attached to the laminate. ×: A part of the AR layer precursor film is attached to the base material 2, and / or a region where the AR layer precursor film is not attached to the laminate is observed.
[0210] <Curvature applicability> The state of the AR layer in the cover glass manufactured in each example was observed. Based on the observation results, the curvature applicability was evaluated according to the following criteria. (Curvature applicability evaluation criteria) ○: No cracks or fractures are observed in the AR layer. ×: Cracks or fractures are observed in the AR layer.
[0211] (Transferability evaluation criteria) ○: No adhesion of the AR layer and / or the adhesive layer is observed on the peeling surface of the peeled base material 2. ×: Adhesion of the AR layer and / or the adhesive layer is observed on the peeling surface of the peeled base material 2.
[0212] [Results] Table 1 shows the composition of the composition used to form each member, the production conditions, and the evaluation results for each example of cover glass. In the "AR layer" column in the table, "organic" means that the AR layer is a layer formed using the above composition R, and "metal oxide" means that the AR layer is an inorganic film formed from the above metal oxide.
[0213] [Table 2]
[0214] As shown in Table 1 above, the cover glasses of Examples 1 to 7 each include a glass substrate having a first main surface and a second main surface, at least a portion of the first main surface being a curved region, an adhesive layer disposed on the first main surface and containing an acrylic resin and a silane coupling agent, and an antireflection layer disposed on the adhesive layer. The antireflection layer of each of the cover glasses was confirmed to have excellent glass adhesion and surface pencil hardness.
[0215] In contrast, in the cover glass of Example 8, in which the AR layer did not contain a resin component, it was not possible to arrange an adhesive layer and an AR layer on the curved area of the surface of the glass substrate, and in the cover glasses of Examples 9 to 12, in which the adhesive layer did not contain either an acrylic resin or a silane coupling agent, it was confirmed that either the glass adhesion or the surface pencil hardness was inferior. [Explanation of symbols]
[0216] 1. Glass substrate 3 Colored layer 4 Adhesive layer 5 AR layer (anti-reflection layer) 6 AFP layer (stain-resistant layer) 7 Colored area 8 Opening area 10 Coverslip 11 First main surface 12 Second main surface 13,21,31,41 curved area 14,22 Planar area 32,42 midpoint
Claims
1. A glass substrate having a first main surface and a second main surface, at least a portion of the first main surface being a curved region; an adhesive layer disposed on the first major surface of the glass substrate; An anti-reflection layer disposed on the adhesive layer, The antireflection layer contains a resin component, The adhesive layer comprises an acrylic resin as a main component and further comprises a silane coupling agent.
2. The cover glass of claim 1, wherein the shape of the curved region is a complex curve that is curved in both a first direction that is a tangent direction of the curved region and a second direction that is a tangent direction of the curved region and different from the first direction at any point P included in the curved region.
3. The cover glass according to claim 2 , wherein the adhesive layer is a resin layer formed using a composition B1 containing an acrylic resin having a reactive group and a silane coupling agent.
4. The cover glass of claim 2, wherein the adhesive layer comprises a resin layer formed using a composition B2 containing an acrylic resin having a reactive group, and a primer layer formed using a composition B3 containing a silane coupling agent.
5. The cover glass of claim 3 or 4, wherein the composition B1 or B2 further comprises a multifunctional urethane (meth)acrylate compound.
6. The cover glass of claim 5 , wherein the composition B1 or B2 further comprises inorganic oxide particles.
7. 5. The cover glass of claim 3, wherein the silane coupling agent has an ethylenically unsaturated group.
8. The cover glass according to claim 3, wherein the content of the silane coupling agent is 1 to 15 mass % based on the total solid content of the composition B1.
9. 5. The cover glass of claim 3 or 4, wherein the antireflective layer comprises an acrylic resin and hollow silica particles.
10. 5. The cover glass according to claim 1, which has a luminous reflectance of 2.0% or less at a wavelength of 360 to 740 nm measured from the antireflection layer side.
11. The cover glass according to any one of claims 1 to 4, further comprising an antifouling layer on the antireflection layer.
12. The antiglare layer further includes an uneven surface formed on at least a part of the surface of the antireflection layer opposite to the adhesive layer, The cover glass according to any one of claims 1 to 4, wherein the uneven structure has an arithmetic mean height Ra of 10 to 100 nm.
13. The cover glass of claim 12 , wherein the adhesive layer further comprises antiglare imparting particles.
14. a colored layer disposed on the second main surface of the glass substrate; The cover glass according to any one of claims 1 to 4, wherein the second main surface has a colored region where the colored layer is laminated and an open region where the colored layer is not laminated.
15. the first main surface has regions with different radii of curvature; The cover glass according to any one of claims 1 to 4, wherein the region of the first main surface where the antireflection layer is disposed satisfies the following requirement 1. Requirement 1: In the curved surface region of the first main surface on which the antireflection layer is formed, three points are arbitrarily selected from the region having the smallest radius of curvature, and the L * Value, a * value and b * The value is measured, and the measured L * Value, a * value and b * The arithmetic mean value L * 1. a * 1 and b * In addition, three points are arbitrarily selected from the area of the first main surface where the antireflection layer is formed, and L * Value, a * value and b * The value is measured, and the measured L * Value, a * value and b * The arithmetic mean value L * 2. a * 2 and b * 2 is then calculated. * 1 and L * Difference ΔL from 2 * , a * 1 and a * Difference Δa from 2 * , and b * 1 and b * Difference from 2 Δb * The color difference ΔE calculated from the above using the following formula (1) is 4 or less. * Value, a * value and b * The value is the L value specified in JIS Z8781-4. * a * b * Lightness in color space L * , and chromaticity a * and b * means... ΔE={(ΔL) * ) 2 +(Yes) * ) 2 + (Δb) * ) 2 } 1/2 formula (1)
16. the first main surface has regions with different radii of curvature; 5. The cover glass according to claim 1, wherein the difference between the total thickness of the adhesive layer and the antireflection layer in a region of the first main surface where the antireflection layer is disposed and the total thickness of the adhesive layer and the antireflection layer in a region of the first main surface where the curvature radius is smallest, is 75 nm or more.
17. A method for producing a cover glass according to any one of claims 1 to 4, comprising the steps of: preparing a glass substrate having a first main surface and a second main surface, at least a portion of the first main surface being a curved region; preparing a transfer member having a transfer substrate, an anti-reflection layer precursor film, and an adhesive film in this order; laminating the transfer member on the glass substrate such that the first main surface of the glass substrate and the adhesive film are in contact with each other; The manufacturing method includes curing the adhesive film and the anti-reflection layer precursor film to form an adhesive layer and an anti-reflection layer disposed on the first main surface.
18. the transfer substrate has an uneven structure on a surface in contact with the antireflection layer precursor film, The method according to claim 17 , wherein an antiglare layer having an uneven structure is formed on a surface of the antireflection layer precursor film by peeling off the transfer substrate.
19. A display device comprising the cover glass according to any one of claims 1 to 4 and a display, The display device, wherein the second main surface side of the glass base faces the display.
Citation Information
Patent Citations
Glass laminate, front plate for display, and display unit
JP2021167959A
Cited By
Attaching manufacturing method of hyperbolic glass display screen
CN119992977A